Binder composition for all-solid-state secondary batteries, slurry composition for all-solid-state secondary batteries, functional layer for all-solid-state secondary batteries, and all-solid-state secondary battery

By using the adhesive composition with ester solvents with more than 6 or more carbon atoms in the base unit and the number of carbon atoms, it solves the problem of the adhesion and internal resistance of the full solid secondary battery, and realizes better adhesive and reduced internal internal internal internal The effect of blocking.

CN119343800APending Publication Date: 2025-01-21ZEON CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380046243.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-23
Filing Date
2023-05-24
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

There is room for improvement in the adhesive composition of existing all-solid secondary batteries in terms of improving adhesion and reducing internal resistance.

Method used

A binder composition containing a specific copolymer and a solvent is used. The copolymer contains a nitrile group-containing monomer unit and an ester solvent with a carbon number of 6 or more. The haze of the copolymer is between 30% and below 80%.

Benefits of technology

While reducing the internal resistance of the all-solid-state secondary battery, it significantly improves the adhesion of the functional layer, thereby enhancing the firm adhesion of the battery materials.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The purpose of the present invention is to provide a binder composition for all-solid-state secondary batteries, which is capable of imparting excellent adhesiveness to a functional layer for all-solid-state secondary batteries while reducing the internal resistance of all-solid-state secondary batteries. The present invention is a binder composition for an all-solid-state secondary battery, the binder composition comprising a copolymer and a solvent, the copolymer containing nitrile group-containing monomer units, the solvent containing an ester solvent having 6 or more carbon atoms, and the content of the monomer units in the copolymer being 100% by mass. The content ratio of the nitrile group-containing monomer unit in the copolymer is from 10% by mass to 22% by mass (inclusive), the tetrahydrofuran insoluble component ratio of the copolymer is from 0.5% by mass to 3% by mass (inclusive), and when the copolymer is dissolved in the solvent such that the concentration of the copolymer is 8% by mass, the content of the tetrahydrofuran insoluble component in the copolymer is 0.5% by mass to 3% by mass (inclusive). The haze of the obtained copolymer solution is 30% or more and 80% or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an adhesive composition for an all-solid-state secondary battery, a slurry composition for an all-solid-state secondary battery, a functional layer for an all-solid-state secondary battery and an all-solid-state secondary battery. Background Art

[0002] In recent years, the demand for secondary batteries such as lithium-ion batteries has been increasing in various applications, including mobile terminals such as mobile information terminals and mobile electronic devices, as well as small household power storage devices, electric two-wheeled vehicles, electric vehicles, and hybrid electric vehicles.

[0003] As the use expands, the safety of secondary batteries is required to be further improved. In order to ensure the safety of secondary batteries, for example, a method of preventing leakage of an organic electrolyte formed by dissolving an electrolyte in an organic solvent is effective. On the other hand, the technology of making a secondary battery (all-solid-state secondary battery) having a solid electrolyte layer instead of a flammable organic electrolyte and all components in a solid state has also been explored.

[0004] Specifically, an all-solid-state secondary battery generally has a solid electrolyte layer as an electrolyte layer between the positive electrode and the negative electrode. Here, when making an all-solid-state secondary battery, a binder is generally used. The binder can be used, for example, in the solid electrolyte layer, in the electrode composite material layer of the electrode formed by arranging the electrode composite material layer on the current collector (hereinafter, there is a case where the solid electrolyte layer and the electrode composite material layer are collectively referred to as "all-solid-state secondary battery functional layer") to bond functional particles such as solid electrolyte particles and electrode active material particles to prevent these functional particles from detaching from battery materials such as the solid electrolyte layer and the electrode.

[0005] For example, Patent Document 1 describes an all-solid-state secondary battery comprising a positive electrode having a positive electrode active material layer (positive electrode composite material layer), a negative electrode having a negative electrode active material layer (negative electrode composite material layer), and a solid electrolyte layer located between the positive electrode active material layer and the negative electrode active material layer. It describes the use of a slurry composition comprising functional particles, a specified polymer as a binder, and an organic solvent to form the positive electrode active material layer, the negative electrode active material layer, or the solid electrolyte layer.

[0006] In addition, Patent Document 2 describes that a slurry prepared by mixing an active material, a conductive material, a sulfide-based solid electrolyte, a specified binder and a solvent is applied to a substrate to form a cathode of an all-solid-state lithium-ion battery, and also describes an all-solid-state lithium-ion battery having the cathode.

[0007] These slurry compositions in Patent Documents 1 and 2 use a nitrile polymer as a binder and xylene, cyclopentyl methyl ether (CPME), or the like as a solvent.

[0008] Prior art literature Patent Literature Patent document 1: Japanese Patent No. 5768815; Patent document 2: Japanese Patent Application Publication No. 2020-525992. Summary of the invention

[0009] Problem that the invention aims to solve Here, in an all-solid-state secondary battery, it is desired that the functional layer for the all-solid-state secondary battery has excellent adhesion to the battery material (e.g., current collector) that is in contact with the functional layer for the all-solid-state secondary battery, and there is room for further improvement in the existing adhesive composition in terms of imparting excellent adhesion to the functional layer for the all-solid-state secondary battery.

[0010] Furthermore, all-solid-state secondary batteries are expected to have low internal resistance, and existing adhesive compositions also have room for further improvement in reducing the internal resistance of all-solid-state secondary batteries.

[0011] Therefore, an object of the present invention is to provide an adhesive composition for an all-solid-state secondary battery that can reduce the internal resistance of the all-solid-state secondary battery and impart excellent adhesion to a functional layer for the all-solid-state secondary battery.

[0012] Another object of the present invention is to provide a slurry composition for an all-solid-state secondary battery that can reduce the internal resistance of the all-solid-state secondary battery and impart excellent adhesion to a functional layer for the all-solid-state secondary battery.

[0013] Another object of the present invention is to provide a functional layer for an all-solid-state secondary battery that can reduce the internal resistance of the all-solid-state secondary battery and exhibit excellent adhesiveness.

[0014] Another object of the present invention is to provide an all-solid-state secondary battery in which battery materials are firmly bonded to each other while reducing internal resistance.

[0015] Solutions for solving problems The present inventors have conducted in-depth research for the purpose of solving the above problems. Then, the present inventors found that if a binder composition for an all-solid-state secondary battery is used, which comprises a prescribed copolymer and a prescribed solvent, and the haze of the copolymer solution obtained when the copolymer is dissolved in the solvent in a manner such that the concentration of the copolymer becomes 8% by mass is within a prescribed range, the above problems can be solved, thereby completing the present invention.

[0016] That is, the object of the present invention is to advantageously solve the above-mentioned problems. [1] The present invention is a binder composition for an all-solid-state secondary battery, comprising a copolymer and a solvent, wherein the copolymer contains a nitrile group-containing monomer unit, and the solvent contains an ester solvent having 6 or more carbon atoms, and when all repeating units in the copolymer are set to 100% by mass, the content ratio of the nitrile group-containing monomer unit in the copolymer is 10% by mass or more and 22% by mass or less, and the tetrahydrofuran-insoluble component rate of the copolymer is 0.5% by mass or more and 3% by mass or less, and when the copolymer is dissolved in the solvent in a manner such that the concentration of the copolymer becomes 8% by mass, the haze of the obtained copolymer solution is 30% or more and 80% or less.

[0017] When the binder composition for an all-solid-state secondary battery is used, it is possible to reduce the internal resistance of the all-solid-state secondary battery and provide excellent adhesion to the functional layer for the all-solid-state secondary battery.

[0018] In the present specification, the "monomer unit" of a (co)polymer means "a repeating unit derived from the monomer contained in a polymer obtained by using the monomer".

[0019] In this specification, the content ratio of various repeating units (monomer units and structural units) in the copolymer can be expressed as follows: 1 The determination was carried out by nuclear magnetic resonance (NMR) methods such as H-NMR.

[0020] In the present specification, the tetrahydrofuran-insoluble content can be measured by the method described in Examples of the present specification.

[0021] In the present specification, the haze of the copolymer solution can be measured by the method described in Examples of the present specification.

[0022] [2] In the binder composition for an all-solid-state secondary battery according to [1] above, the iodine value of the copolymer is preferably 0.5 mg / 100 mg or more and 30 mg / 100 mg or less.

[0023] When the iodine value of the copolymer is not less than the above lower limit, a decrease in the cycle characteristics of the all-solid-state secondary battery can be effectively suppressed.

[0024] On the other hand, when the iodine value of the copolymer is not more than the above upper limit, the cycle characteristics of the all-solid-state secondary battery can be further improved.

[0025] In the present specification, the iodine value of the copolymer can be measured by the method described in Examples of the present specification.

[0026] [3] In the binder composition for an all-solid-state secondary battery of [1] or [2], the copolymer preferably further contains an alkylene structural unit, the alkylene structural unit is a 1,3-butadiene hydride unit, and the nitrile group-containing monomer unit is an acrylonitrile unit.

[0027] If the copolymer contains the above monomer units, it can give the functional layer for all-solid-state secondary batteries more excellent adhesion. In addition, if the copolymer contains the above monomer units, it can further improve the dispersibility of the functional particles in the slurry composition for all-solid-state secondary batteries prepared using the binder composition for all-solid-state secondary batteries.

[0028] [4] In the binder composition for an all-solid-state secondary battery according to any one of [1] to [3] above, the copolymer preferably contains a (meth)acrylate monomer unit having an alkyl group having 4 to 9 carbon atoms.

[0029] When the copolymer contains a (meth)acrylate monomer unit having an alkyl group having 4 to 9 carbon atoms, the internal resistance of the all-solid-state secondary battery can be further reduced.

[0030] [5] In the binder composition for an all-solid-state secondary battery of the above-mentioned [4], preferably, when all repeating units in the above-mentioned copolymer are set to 100 mass %, the content ratio of the above-mentioned (meth)acrylate monomer units having an alkyl group with a carbon number of 4 or more and 9 or less in the above-mentioned copolymer is 25 mass % or more and 45 mass % or less.

[0031] When the content ratio of the (meth)acrylate monomer units having an alkyl group having 4 to 9 carbon atoms in the copolymer is greater than the above lower limit when all repeating units in the copolymer are 100 mass %, the internal resistance of the all-solid secondary battery can be further reduced.

[0032] On the other hand, if the content ratio of the (meth) acrylate monomer unit with an alkyl group having a carbon number of 4 or more and 9 or less in the copolymer is below the above upper limit when all repeating units in the copolymer are set to 100% by mass, the internal resistance of the all-solid-state secondary battery can be further reduced. In addition, the cycle characteristics of the all-solid-state secondary battery can be further improved.

[0033] [6] In the binder composition for an all-solid-state secondary battery according to any one of [1] to [5] above, the copolymer preferably has a hydrophilic group.

[0034] When the copolymer has a hydrophilic group, it is possible to impart more excellent adhesiveness to the functional layer for an all-solid-state secondary battery.

[0035] In addition, the object of the present invention is to advantageously solve the above-mentioned problems. [7] The present invention is a slurry composition for an all-solid-state secondary battery, which comprises functional particles and the binder composition for an all-solid-state secondary battery according to any one of [1] to [6].

[0036] The slurry composition for an all-solid-state secondary battery can provide excellent adhesion to the functional layer for an all-solid-state secondary battery while reducing the internal resistance of the all-solid-state secondary battery.

[0037] [8] In the slurry composition for an all-solid-state secondary battery according to [7], the functional particles are preferably at least one of solid electrolyte particles and electrode active material particles.

[0038] If the functional particles are at least any one of solid electrolyte particles and electrode active material particles, the functional layer for an all-solid-state secondary battery can be endowed with functions as a solid electrolyte layer and / or an electrode composite material layer.

[0039] Furthermore, the present invention aims to advantageously solve the above-mentioned problems. [9] The present invention is a functional layer for an all-solid-state secondary battery, which is formed using the slurry composition for an all-solid-state secondary battery of [7] or [8] above.

[0040] The functional layer for an all-solid-state secondary battery can exhibit excellent adhesiveness while reducing the internal resistance of the all-solid-state secondary battery.

[0041] In addition, the present invention aims to advantageously solve the above-mentioned problems.

[10] The present invention is an all-solid-state secondary battery having the functional layer for an all-solid-state secondary battery according to [9] above.

[0042] The above-described all-solid-state secondary battery can reduce internal resistance and allow battery materials to be firmly bonded to each other.

[0043] Effects of the Invention According to the present invention, it is possible to provide an adhesive composition for an all-solid-state secondary battery that can reduce the internal resistance of the all-solid-state secondary battery and impart excellent adhesion to a functional layer for the all-solid-state secondary battery.

[0044] Furthermore, according to the present invention, it is possible to provide a slurry composition for an all-solid-state secondary battery that can reduce the internal resistance of the all-solid-state secondary battery and impart excellent adhesion to the functional layer for the all-solid-state secondary battery.

[0045] Furthermore, according to the present invention, it is possible to provide a functional layer for an all-solid-state secondary battery that can reduce the internal resistance of the all-solid-state secondary battery and exhibit excellent adhesiveness.

[0046] Furthermore, according to the present invention, it is possible to provide an all-solid-state secondary battery in which battery materials are firmly bonded to each other while reducing internal resistance. DETAILED DESCRIPTION

[0047] Hereinafter, embodiments of the present invention will be described in detail.

[0048] Here, the binder composition for all-solid-state secondary batteries of the present invention (hereinafter, sometimes referred to as "binder composition") can be used to prepare the slurry composition for all-solid-state secondary batteries of the present invention (hereinafter, sometimes referred to as "slurry composition"). In addition, the slurry composition of the present invention can be used to form functional layers for all-solid-state secondary batteries such as solid electrolyte layers and electrode composite material layers (hereinafter, sometimes referred to as "functional layers"). Moreover, the all-solid-state secondary battery of the present invention has a functional layer of the present invention formed using the slurry composition of the present invention.

[0049] (Binder composition for all-solid-state secondary batteries) The binder composition for all-solid-state secondary batteries of the present invention comprises a prescribed copolymer and a prescribed solvent. Here, the solvent contains an ester solvent having a carbon number of 6 or more. In addition, the copolymer contains a nitrile-containing monomer unit. Furthermore, when all repeating units in the copolymer are set to 100% by mass, the content ratio of the nitrile-containing monomer unit in the copolymer is 10% by mass or more and 22% by mass or less, and the tetrahydrofuran insoluble component rate of the copolymer (hereinafter, sometimes referred to as "THF insoluble component rate") is 0.5% by mass or more and 3% by mass or less. Moreover, for the copolymer and the solvent, when the copolymer is dissolved in the solvent in a manner such that the concentration of the copolymer becomes 8% by mass, the haze of the obtained copolymer solution satisfies 30% or more and 80% or less. In addition, the binder composition of the present invention may also contain other components arbitrarily in addition to the above-mentioned prescribed copolymer and prescribed solvent. As other components, surfactants, dispersants, antioxidants, etc. can be cited.

[0050] The above-mentioned binder composition can reduce the internal resistance of the all-solid-state secondary battery and provide excellent adhesion to the functional layer. In addition, the above-mentioned binder composition can improve the cycle characteristics of the all-solid-state secondary battery.

[0051] <Copolymer> The copolymer is a component that can prevent the functional particles contained in the functional layer from being separated from the functional layer.

[0052] Here, the copolymer has the above-mentioned prescribed composition and characteristics, and preferably has a hydrophilic group from the aspect of being able to impart a more excellent adhesion to the functional layer. Examples of the hydrophilic group include a carboxyl group, a sulfonic acid group, a phosphoric acid group, a hydroxyl group, etc. Among these, from the aspect of being able to impart a more excellent adhesion to the functional layer, a carboxyl group and a hydroxyl group are preferred, and a hydroxyl group is more preferred. The copolymer may have only one of these hydrophilic groups, or may have two or more.

[0053] There is no particular limitation on the method for introducing hydrophilic groups into copolymers. A copolymer can be prepared using a monomer composition comprising a hydrophilic group-containing monomer described later, thereby obtaining a copolymer containing a hydrophilic group-containing monomer unit. Alternatively, a copolymer having a specified composition can be modified (e.g., terminal modification) to obtain a copolymer having the above-mentioned hydrophilic group. The former is preferred.

[0054] <<Composition of copolymer>> The copolymer contains a nitrile group-containing monomer unit, and optionally contains a conjugated diene monomer unit, an alkylene structural unit, a hydrophilic group-containing monomer unit, a (meth)acrylate monomer unit having an alkyl group having 4 to 9 carbon atoms, and an aromatic vinyl monomer unit.

[0055] In addition, in this specification, "(meth)acrylic acid" means "acrylic acid and / or methacrylic acid".

[0056] [Nitrile-containing monomer unit] The nitrile group-containing monomer unit is a repeating unit derived from a nitrile group-containing monomer.

[0057] As the nitrile-containing monomer capable of forming the nitrile-containing monomer unit, α, β-ethylenically unsaturated nitrile monomer can be cited. Moreover, as the α, β-ethylenically unsaturated nitrile monomer, there is no particular limitation as long as it is an α, β-ethylenically unsaturated compound having a nitrile group, and examples thereof include: acrylonitrile; α-halogenated acrylonitrile such as α-chloroacrylonitrile and α-bromoacrylonitrile; α-alkyl acrylonitrile such as methacrylonitrile and α-ethylacrylonitrile, etc. Among these, as the nitrile-containing monomer, acrylonitrile and methacrylonitrile are preferred, and acrylonitrile is more preferred from the aspect of being able to impart better adhesion to the functional layer. These can be used alone or in combination of two or more.

[0058] In the adhesive composition of the present invention, when all repeating units in the copolymer are set to 100% by mass, the content ratio of the nitrile-containing monomeric unit in the copolymer is 10% by mass or more and 22% by mass or less. Moreover, when all repeating units in the copolymer are set to 100% by mass, the content ratio of the nitrile-containing monomeric unit in the copolymer is preferably 12% by mass or more, more preferably 14% by mass or more, preferably 20.5% by mass or less, and more preferably 19% by mass or less.

[0059] When the content of the nitrile group-containing monomer unit in the copolymer is 10% by mass or more, based on 100% by mass of all repeating units in the copolymer, the adhesiveness of the copolymer itself is improved, and excellent adhesiveness can be imparted to the functional layer.

[0060] On the other hand, when all repeating units in the copolymer are set to 100% by mass, if the content ratio of the nitrile-containing monomer unit in the copolymer is below 22% by mass, the functional layer can be given excellent adhesion. The reason is inferred to be that the solubility of the copolymer in the solvent is improved, and a slurry composition well dispersed by functional particles can be obtained. Therefore, when such a slurry composition is used for the formation of a functional layer, a functional layer well dispersed by functional particles can be formed. In addition, since functional particles can be well dispersed in the functional layer, the internal resistance of the all-solid-state secondary battery can be reduced, and the cycle characteristics of the all-solid-state secondary battery can be improved.

[0061] [Conjugated diene monomer unit] The conjugated diene monomer unit is a repeating unit derived from a conjugated diene monomer.

[0062] Examples of the conjugated diene monomer capable of forming the conjugated diene monomer unit include conjugated diene compounds such as 1,3-butadiene, isoprene, 2,3-dimethyl-1,3-butadiene, and 1,3-pentadiene. Among them, 1,3-butadiene is preferred. These can be used alone or in combination of two or more.

[0063] When all repeating units in the copolymer are taken as 100% by mass, the content ratio of the conjugated diene monomer unit in the copolymer is preferably 10% by mass or less, and more preferably 5% by mass or less.

[0064] On the other hand, when all repeating units in the copolymer are taken as 100% by mass, the content ratio of the conjugated diene monomer unit in the copolymer is, for example, 0.5% by mass or more, or 1% by mass or more.

[0065] [Alkylene structural unit] The alkylene structural unit is composed only of the general formula: -C n H 2n - [wherein n is an integer greater than or equal to 2] The copolymer contains an alkylene structural unit, which can improve the dispersibility of the functional particles in the slurry composition prepared using the binder composition.

[0066] The alkylene structural unit may be linear or branched. From the viewpoint of further improving the dispersibility of the functional particles in the slurry composition, the alkylene structural unit is preferably linear, i.e., a linear alkylene structural unit. In addition, the alkylene structural unit preferably has 4 or more carbon atoms (i.e., the general formula -C n H 2n - wherein n is an integer greater than 4).

[0067] The method for introducing the alkylene structural unit into the copolymer is not particularly limited, and examples thereof include the following method (1) or (2): (1) a method of preparing a copolymer from a monomer composition comprising the above-mentioned conjugated diene monomer, and hydrogenating (adding hydrogen) the copolymer to thereby convert the conjugated diene monomer unit into an alkylene structural unit; (2) A method for producing a copolymer from a monomer composition containing a 1-olefin monomer. Among these, the method (1) is preferred because the copolymer can be easily produced.

[0068] As the conjugated diene monomer that can be used in the method of (1) above, for example, conjugated diene compounds such as 1,3-butadiene, isoprene, 2,3-dimethyl-1,3-butadiene, and 1,3-pentadiene can be cited. Among them, 1,3-butadiene is preferred. These can be used alone or in combination of two or more. Here, the alkylene structural unit is preferably a structural unit (conjugated diene hydride unit) obtained by hydrogenating (hydrogenating) the conjugated diene monomer unit. In addition, from the aspect of being able to further improve the dispersibility of the functional particles in the slurry composition prepared using the binder composition, the alkylene structural unit is more preferably a structural unit (1,3-butadiene hydride unit) obtained by hydrogenating the 1,3-butadiene unit. Moreover, hydrogenation can be carried out using a known method described later.

[0069] On the other hand, examples of 1-olefin monomers that can be used in the method (2) include 1-butene and 1-hexene.

[0070] These conjugated diene monomers and 1-olefin monomers can be used alone or in combination of two or more.

[0071] When the alkylene structural unit is introduced into the copolymer by the method (1) above, if the conjugated diene monomer unit is not completely hydrogenated, the conjugated diene monomer unit may remain in the copolymer.

[0072] When all repeating units (the total of structural units and monomer units) in the copolymer are set to 100% by mass, the total content ratio of the alkylene structural units and the conjugated diene monomer units in the copolymer is preferably 30% by mass or more, more preferably 40% by mass or more, preferably 70% by mass or less, more preferably 60% by mass or less, and further preferably 50% by mass or less.

[0073] When all repeating units in the copolymer are 100 mass %, if the total content ratio of the alkylene structural unit and the conjugated diene monomer unit in the copolymer is within the above range, the dispersibility of the functional particles in the slurry composition prepared using the binder composition can be further improved.

[0074] In addition, when the copolymer does not contain a conjugated diene monomer unit, for example, when the conjugated diene monomer unit is completely hydrogenated in the method (1) above or when the copolymer is produced according to the method (2) above, when all repeating units (the sum of structural units and monomer units) in the copolymer are set to 100% by mass, the content ratio of the alkylene structural unit in the copolymer is preferably 30% by mass or more, more preferably 40% by mass or more, preferably 70% by mass or less, more preferably 60% by mass or less, and further preferably 50% by mass or less.

[0075] When the content ratio of the alkylene structural unit in the copolymer is within the above range, assuming that all repeating units in the copolymer are 100 mass %, the dispersibility of the functional particles in the slurry composition prepared using the binder composition can be further improved.

[0076] [Hydrophilic group-containing monomer unit] The hydrophilic group-containing monomer unit is a repeating unit derived from a hydrophilic group-containing monomer. When the copolymer contains the hydrophilic group-containing monomer unit, it is possible to impart more excellent adhesiveness to the functional layer.

[0077] Examples of the hydrophilic group-containing monomer capable of forming the hydrophilic group-containing monomer unit include monomers having a carboxylic acid group, monomers having a sulfonic acid group, monomers having a phosphoric acid group, monomers having a hydroxyl group, etc. These monomers can be used alone or in combination of two or more.

[0078] Examples of the monomer having a carboxylic acid group include monocarboxylic acids and derivatives thereof, dicarboxylic acids and anhydrides thereof, and derivatives thereof.

[0079] Examples of the monocarboxylic acid include acrylic acid, methacrylic acid, and crotonic acid.

[0080] Examples of the monocarboxylic acid derivative include 2-ethylacrylic acid, isocrotonic acid, α-acetoxyacrylic acid, β-trans-aryloxyacrylic acid, α-chloro-β-E-methoxyacrylic acid, and β-diaminoacrylic acid.

[0081] Examples of the dicarboxylic acid include maleic acid, fumaric acid, and itaconic acid.

[0082] Examples of the dicarboxylic acid derivatives include maleic acid esters such as methylmaleic acid, dimethylmaleic acid, phenylmaleic acid, chloromaleic acid, dichloromaleic acid, fluoromaleic acid, methylallyl maleate, diphenyl maleate, nonyl maleate, decyl maleate, dodecyl maleate, octadecyl maleate, and fluoroalkyl maleate.

[0083] Examples of the anhydride of dicarboxylic acid include maleic anhydride, acrylic anhydride, methylmaleic anhydride, and dimethylmaleic anhydride.

[0084] Furthermore, as the monomer having a carboxylic acid group, an acid anhydride that generates a carboxyl group by hydrolysis can also be used.

[0085] Other examples include monoesters and diesters of α,β-ethylenically unsaturated polycarboxylic acids such as monoethyl maleate, diethyl maleate, monobutyl maleate, dibutyl maleate, monoethyl fumarate, diethyl fumarate, monobutyl fumarate, dibutyl fumarate, monocyclohexyl fumarate, dicyclohexyl fumarate, monoethyl itaconate, diethyl itaconate, monobutyl itaconate, and dibutyl itaconate.

[0086] Among the above, monocarboxylic acids are preferred, and methacrylic acid is more preferred.

[0087] Examples of the monomer having a sulfonic acid group include vinyl sulfonic acid, methylvinyl sulfonic acid, (meth)allyl sulfonic acid, styrene sulfonic acid, 2-sulfonic ethyl (meth)acrylate, 2-acrylamido-2-methylpropanesulfonic acid, and 3-allyloxy-2-hydroxypropanesulfonic acid.

[0088] In addition, in this specification, "(meth)allyl group" means an allyl group and / or a methallyl group.

[0089] Examples of the monomer having a phosphoric acid group include 2-(meth)acryloyloxyethyl phosphate, methyl-2-(meth)acryloyloxyethyl phosphate, ethyl-(meth)acryloyloxyethyl phosphate, vinylphosphonic acid, and dimethyl vinylphosphonate.

[0090] In addition, in this specification, "(meth)acryloyl group" means an acryloyl group and / or a methacryloyl group.

[0091] Examples of monomers having a hydroxyl group include: ethylenically unsaturated alcohols such as (meth)allyl alcohol, 3-butene-1-ol, and 5-hexene-1-ol; alkyl alcohol esters of ethylenically unsaturated carboxylic acids such as 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, 1,4-cyclohexanedimethanol monoacrylate, 2-hydroxyethyl methacrylate, 2-hydroxypropyl methacrylate, di-2-hydroxyethyl maleate, di-4-hydroxybutyl maleate, and di-2-hydroxypropyl itaconate; and alkyl alcohol esters of ethylenically unsaturated carboxylic acids such as 2-hydroxyethyl acrylate, 2-hydroxypropyl methacrylate, and di-2-hydroxyethyl maleate. 1 -COO-(C n H 2n O) m -H (wherein, m represents an integer of 2 to 9, n represents an integer of 2 to 4, R 1 Esters of polyalkylene glycol represented by (methyl) and (meth)acrylic acid; mono(meth)acrylates of dihydroxy esters of dicarboxylic acids such as 2-hydroxyethyl-2'-(meth)acryloyloxyphthalate and 2-hydroxyethyl-2'-(meth)acryloyloxysuccinate; vinyl ethers such as 2-hydroxyethyl vinyl ether and 2-hydroxypropyl vinyl ether; (meth)allyl-2-hydroxyethyl ether, (meth)allyl-2-hydroxypropyl ether, (meth)allyl-3-hydroxypropyl ether, (meth)allyl-2-hydroxybutyl ether, (meth)allyl-3-hydroxybutyl ether, (meth)allyl-4-hydroxybutyl ether, (meth)allyl-6-hydroxybutyl ether. Mono(meth)allyl ethers of alkylene glycols such as hydroxyhexyl ether; mono(meth)allyl ethers of polyoxyalkylene glycols such as diethylene glycol mono(meth)allyl ether and dipropylene glycol mono(meth)allyl ether; mono(meth)allyl ethers of halogen-substituted and hydroxy-substituted (poly)alkylene glycols such as glycerol mono(meth)allyl ether, (meth)allyl-2-chloro-3-hydroxypropyl ether and (meth)allyl-2-hydroxy-3-chloropropyl ether; mono(meth)allyl ethers of polyphenols such as eugenol and isoeugenol and their halogen-substituted products; (meth)allyl sulfide ethers of alkylene glycols such as (meth)allyl-2-hydroxyethyl sulfide and (meth)allyl-2-hydroxypropyl sulfide, etc.

[0092] Among the above, alkanol esters of ethylenically unsaturated carboxylic acids are preferred, and 1,4-cyclohexanedimethanol monoacrylate and 2-hydroxyethyl methacrylate are more preferred.

[0093] From the viewpoint of further improving the dispersibility of the functional particles in the slurry composition prepared using the binder composition, as the hydrophilic group-containing monomer, it is preferred to use a monomer having a carboxylic acid group (carboxylic acid group-containing monomer) and / or a monomer having a hydroxyl group (hydroxyl group-containing monomer unit), and it is more preferred to use a hydroxyl group-containing monomer unit.

[0094] When all repeating units in the copolymer are set to 100% by mass, the content ratio of the hydrophilic group-containing monomer unit in the copolymer is preferably 1% by mass or more, more preferably 1.5% by mass or more, further preferably 2% by mass or more, preferably 10% by mass or less, more preferably 8% by mass or less, further preferably 6% by mass or less.

[0095] When the content of the hydrophilic group-containing monomer unit in the copolymer is equal to or greater than the above lower limit, the adhesiveness of the copolymer itself is further improved, and more excellent adhesiveness can be imparted to the functional layer.

[0096] On the other hand, when all repeating units in the copolymer are 100% by mass, if the proportion of the hydrophilic group-containing monomer unit in the copolymer is below the above upper limit, the functional layer can be given more excellent adhesion. The reason is speculated to be that the solubility of the copolymer in the solvent is further improved, and a slurry composition that is more well dispersed by functional particles, etc. can be obtained. Therefore, when such a slurry composition is used for the formation of a functional layer, a functional layer that is more well dispersed by functional particles, etc. can be formed. In addition, since functional particles, etc. can be more well dispersed in the functional layer, the internal resistance of the all-solid-state secondary battery can be further reduced, and the cycle characteristics of the all-solid-state secondary battery can be further improved.

[0097] [(Meth)acrylate monomer unit having an alkyl group having 4 to 9 carbon atoms] The (meth)acrylate monomer unit having an alkyl group with a carbon number of 4 to 9 is a repeating unit derived from a (meth)acrylate monomer having an alkyl group with a carbon number of 4 to 9. The copolymer contains the (meth)acrylate monomer unit having an alkyl group with a carbon number of 4 to 9, so that the dispersibility of the functional particles in the slurry composition prepared using the binder composition can be further improved, and as a result, the internal resistance of the all-solid-state secondary battery can be further reduced.

[0098] Here, "having an alkyl group having 4 to 9 carbon atoms" means that the non-carbonyl oxygen atom of the (meth)acrylate monomer is bonded to an alkyl group having 4 to 9 carbon atoms. The alkyl group having 4 to 9 carbon atoms may be linear, branched, or cyclic, but is preferably linear in terms of ease of preparation of a copolymer.

[0099] In addition, the (meth)acrylate monomer units having an alkyl group with a carbon number of 4 to 9 do not include the above-mentioned hydrophilic group-containing monomer units. That is, for example, a monomer unit in which a hydroxyl group is bonded to an alkyl group with a carbon number of 4 to 9 is not included in the (meth)acrylate monomer units having an alkyl group with a carbon number of 4 to 9.

[0100] In the (meth)acrylic acid ester monomer unit having an alkyl group having 4 to 9 carbon atoms, the alkyl group preferably has 8 or less carbon atoms, and more preferably has 6 or less carbon atoms.

[0101] When the number of carbon atoms of the alkyl group is at most the above upper limit, a copolymer can be easily produced.

[0102] Here, examples of the C4-C9 (meth)acrylate monomers that can form a (meth)acrylate monomer having an alkyl group having 4 to 9 carbon atoms (hereinafter, sometimes referred to as "C4-C9 (meth)acrylate monomer") unit include alkyl acrylates such as n-butyl acrylate, tert-butyl acrylate, isobutyl acrylate, n-pentyl acrylate, isopentyl acrylate, hexyl acrylate, heptyl acrylate, octyl acrylate, 2-ethylhexyl acrylate, and nonyl acrylate; and alkyl methacrylates such as n-butyl methacrylate, tert-butyl methacrylate, isobutyl methacrylate, n-pentyl methacrylate, isopentyl methacrylate, hexyl methacrylate, heptyl methacrylate, octyl methacrylate, 2-ethylhexyl methacrylate, and nonyl methacrylate. Among them, n-butyl acrylate is preferred.

[0103] These can be used alone or in combination of two or more.

[0104] When all repeating units in the copolymer are set to 100% by mass, the content ratio of the C4-C9 (meth)acrylate monomer units in the copolymer is preferably 25% by mass or more, more preferably 27.5% by mass or more, further preferably 30% by mass or more, preferably 45% by mass or less, more preferably 42.5% by mass or less, further preferably 40% by mass or less.

[0105] When all repeating units in the copolymer are set to 100% by mass, if the content ratio of the C4-C9 (meth)acrylate monomer units in the copolymer is above the above lower limit, the dispersibility of the functional particles in the slurry composition prepared using the binder composition can be further improved, and as a result, the internal resistance of the all-solid-state secondary battery can be further reduced.

[0106] On the other hand, when all repeating units in the copolymer are set to 100% by mass, if the ratio of the C4-C9 (methyl) acrylate monomer units in the copolymer is below the above upper limit, the flexibility of the functional layer is further improved, and the adhesion between the functional layer and the layer adjacent to the functional layer is further improved, and as a result, the internal resistance of the all-solid-state secondary battery can be further reduced. In addition, since the adhesion between the functional layer and the layer adjacent to the functional layer is further improved, the cycle characteristics of the all-solid-state secondary battery can be further improved.

[0107] [Aromatic vinyl monomer unit] The aromatic vinyl monomer unit is a repeating unit derived from an aromatic vinyl monomer.

[0108] Examples of the aromatic vinyl monomer capable of forming the aromatic vinyl monomer unit include styrene, α-methylstyrene, vinyltoluene, divinylbenzene, etc. These can be used alone or in combination of two or more.

[0109] When all repeating units in the copolymer are set to 100% by mass, the content ratio of the aromatic vinyl monomer unit in the copolymer is preferably 1% by mass or more, more preferably 5% by mass or more, further preferably 8% by mass or more, preferably 30% by mass or less, more preferably 20% by mass or less, further preferably 12% by mass or less.

[0110] [Other monomer units] The copolymer may contain monomer units other than the above-mentioned nitrile group-containing monomer units, conjugated diene monomer units, alkylene structural units, hydrophilic group-containing monomer units, C4-C9 (meth)acrylate monomer units and aromatic vinyl monomer units (hereinafter sometimes referred to as "other monomer units") as repeating units.

[0111] Examples of other monomer units include (meth)acrylate monomer units having an alkyl group other than an alkyl group having 4 to 9 carbon atoms, that is, (meth)acrylate monomer units having an alkyl group having 3 or less carbon atoms, (meth)acrylate monomer units having an alkyl group having 10 or more carbon atoms, and the like.

[0112] Examples of the (meth)acrylate monomer that can form a (meth)acrylate monomer unit having an alkyl group having 3 or less carbon atoms include methyl acrylate, ethyl acrylate, n-propyl acrylate, isopropyl acrylate, methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, and isopropyl methacrylate.

[0113] Examples of the (meth)acrylate monomer that can form a (meth)acrylate monomer unit having an alkyl group having 10 or more carbon atoms include decyl acrylate, lauryl acrylate, n-tetradecyl acrylate, stearyl acrylate, decyl methacrylate, lauryl methacrylate, n-tetradecyl methacrylate, and stearyl methacrylate.

[0114] When all repeating units in the copolymer are set to 100% by mass, the content ratio of other monomer units in the copolymer is preferably 5% by mass or less, more preferably 4% by mass or less, further preferably 3% by mass or less, further preferably 2% by mass or less, further preferably 1% by mass or less, and particularly preferably 0% by mass. That is, the copolymer particularly preferably does not contain other monomer units.

[0115] <<Method for preparing copolymer>> The preparation method of the above-mentioned copolymer is not particularly limited, and any method such as solution polymerization, suspension polymerization, bulk polymerization, emulsion polymerization, etc. can be used. Among these, emulsion polymerization is preferably used. In addition, as a polymerization method, addition polymerization such as ionic polymerization, free radical polymerization, and living free radical polymerization can be used. In addition, as a polymerization initiator, a known polymerization initiator can be used.

[0116] Here, as a polymerization initiator, for example, inorganic peroxides such as potassium persulfate, sodium persulfate, ammonium persulfate, potassium perphosphate, and hydrogen peroxide can be cited; organic peroxides such as tert-butyl peroxide, cumene hydroperoxide, tert-butyl peroxide, tert-butyl peroxide, acetyl peroxide, isobutyryl peroxide, octanoyl peroxide, dibenzoyl peroxide, 3,5,5-trimethylhexanoyl peroxide, and tert-butyl peroxyisobutyrate; azo compounds such as azobisisobutyronitrile, azobis-2,4-dimethylvaleronitrile, azobiscyclohexanecarbonitrile, and methyl azobisisobutyrate, etc. These polymerization initiators can be used alone or in combination of two or more. As a polymerization initiator, an inorganic or organic peroxide is preferred.

[0117] When a peroxide is used as a polymerization initiator, it can also be used as a redox polymerization initiator in combination with a reducing agent such as sodium hydrogen sulfite or ferrous sulfate.

[0118] Here, when the method (1) described above is used, that is, when a method of converting a conjugated diene monomer unit into an alkylene structural unit by hydrogenation (hydrogenation) is used, as a polymerization method for the copolymer before hydrogenation (that is, the copolymer before hydrogenation), it is preferred to use free radical polymerization using a redox polymerization initiator containing an iron-based compound.

[0119] During polymerization, it is preferred to use a molecular weight regulator having a sulfur-containing group such as a mercapto group. As a compound having a mercapto group used as a molecular weight regulator, for example, compounds having a mercapto group having 8 to 12 carbon atoms, such as octyl mercaptan, 2,2,4,6,6-pentamethyl-4-heptyl mercaptan, 2,4,4,6,6-pentamethyl-2-heptyl mercaptan, 2,3,4,6,6-pentamethyl-2-heptyl mercaptan, 2,3,4,6,6-pentamethyl-3-heptyl mercaptan, tert-dodecyl mercaptan, and n-dodecyl mercaptan; compounds having a mercapto group, such as 2,2,4,6,6-pentamethyl-4-octanyl mercaptan, 2,2,4,6,6,8,8-heptamethyl-4-nonyl mercaptan, bis(2-mercaptoethyl) sulfide, methyl 3-mercaptopropionate, and 1-butyl mercaptan. Among them, compounds having a mercapto group having 8 to 12 carbon atoms are preferred, and tert-dodecyl mercaptan is more preferred.

[0120] The polymerization temperature is preferably 7°C or higher, more preferably 8°C or higher, further preferably 9°C or higher, and is preferably 18°C ​​or lower, more preferably 15°C or lower, further preferably 12°C or lower.

[0121] When the polymerization temperature is within the above range, the THF-insoluble content and the weight average molecular weight of the copolymer can be easily adjusted.

[0122] Here, after carrying out, for example, emulsion polymerization, when using the method of (1), preferably, a coagulant such as aluminum sulfate is added to the aqueous dispersion of the obtained pre-hydrogenated copolymer to coagulate it, the pre-hydrogenated copolymer is recovered, and the recovered pre-hydrogenated copolymer (the filtrate in the case of filtration recovery) is hydrogenated (after arbitrarily implementing the "metathesis reaction" described later). At this time, before hydrogenation, the recovered product (filtrate, etc.) can be washed with water, etc. In addition, before adding a coagulant to the aqueous dispersion, an antioxidant such as alkylated phenol can be added.

[0123] The hydrogenation of the copolymer before hydrogenation can be carried out using known hydrogenation methods such as oil layer hydrogenation or water layer hydrogenation. In addition, as the catalyst for hydrogenation, any known selective hydrogenation catalyst can be used without limitation, and palladium catalysts and rhodium catalysts can be used. These can be used in combination of two or more.

[0124] The amount of the hydrogenation catalyst used may be appropriately determined, and is preferably 50 mass ppm or more, more preferably 200 mass ppm or more, further preferably 300 mass ppm or more, and preferably 4000 mass ppm or less, more preferably 2000 mass ppm or less, further preferably 1000 mass ppm or less, calculated as the metal amount of the hydrogenation catalyst relative to the amount of the pre-hydrogenation copolymer to be hydrogenated.

[0125] When the amount of the hydrogenation catalyst used is within the above range, the iodine value of the copolymer can be easily adjusted.

[0126] The hydrogenation of the copolymer before hydrogenation can be carried out, for example, by the method described in Japanese Patent No. 4509792. Specifically, the hydrogenation of the copolymer before hydrogenation can be carried out after performing a metathesis reaction of the copolymer in the presence of a catalyst and a co-olefin.

[0127] Here, as a catalyst for the metathesis reaction, a known ruthenium-based catalyst can be used. Among them, as a catalyst for the metathesis reaction, it is preferred to use Grubbs catalysts such as bis(tricyclohexylphosphine)benzylidene ruthenium dichloride, 1,3-bis(2,4,6-trimethylphenyl)-2-(imidazolidinyl) (dichlorophenylmethylene) (tricyclohexylphosphine) ruthenium. In addition, as a co-olefin, olefins having 2 to 16 carbon atoms such as ethylene, isobutane, and 1-hexane can be used. In addition, as a hydrogenation catalyst for hydrogenation after the metathesis reaction, a known homogeneous hydrogenation catalyst such as Wilkinson catalyst ((PPh3)3RhCl) can be used.

[0128] <<Properties of Copolymer>> [THF insoluble content] In the adhesive composition of the present invention, the THF insoluble content of the copolymer is 0.5% by mass or more and 3% by mass or less. Moreover, the THF insoluble content of the copolymer is preferably 0.75% by mass or more, more preferably 1.0% by mass or more, preferably 2.5% by mass or less, and more preferably 2.0% by mass or less.

[0129] When the THF-insoluble content of the copolymer is 0.5% by mass or more, the copolymer itself has an appropriate strength, and as a result, excellent adhesiveness can be imparted to the functional layer.

[0130] On the other hand, if the THF insoluble component rate of copolymer is below 3 mass %, the flexibility of functional layer improves, and the adhesion between functional layer and the layer adjacent to the functional layer improves, and as a result, the internal resistance of all-solid-state secondary battery can be reduced. In addition, owing to being able to improve the adhesion between functional layer and the layer adjacent to the functional layer, the cycle characteristics of all-solid-state secondary battery can be improved.

[0131] The THF insoluble content of the copolymer can be adjusted by the composition (content ratio of various repeating units) and weight average molecular weight of the copolymer, and the conditions of the method for preparing the copolymer (for example, polymerization temperature).

[0132] [Iodine value] The iodine value of the copolymer is preferably 0.5 mg / 100 mg or more, more preferably 1.0 mg / 100 mg or more, further preferably 2.0 mg / 100 mg or more, and is preferably 30 mg / 100 mg or less, more preferably 15 mg / 100 mg or less, further preferably 10 mg / 100 mg or less.

[0133] Here, in order to make the iodine value of the copolymer less than the above lower limit, it is necessary to use a large amount of catalyst in hydrogenation, and when such a large amount of catalyst is used, the impurities (residual metals, etc.) mixed into the binder composition become more, and as a result, it is possible to reduce the cycle characteristics of the all-solid-state secondary battery. Therefore, if the iodine value of the copolymer is above the above lower limit, it is possible to effectively suppress the reduction of the cycle characteristics of the all-solid-state secondary battery.

[0134] On the other hand, when the iodine value of the copolymer is not more than the upper limit, the occurrence of a side reaction between the copolymer and the functional particles can be suppressed, and as a result, the cycle characteristics of the all-solid-state secondary battery can be further improved.

[0135] The iodine value of the copolymer can be adjusted by, for example, the amount of the hydrogenation catalyst used when hydrogenating the copolymer.

[0136] [Weight average molecular weight (Mw)] The weight average molecular weight of the copolymer is preferably 5,000 or more, more preferably 10,000 or more, further preferably 30,000 or more, further preferably 40,000 or more, and preferably 3,000,000 or less, more preferably 2,000,000 or less, further preferably 1,000,000 or less, further preferably 80,000 or less, further preferably 60,000 or less.

[0137] When the weight average molecular weight is equal to or greater than the above lower limit, more excellent adhesion can be imparted to the functional layer. In addition, the cycle characteristics of the all-solid-state secondary battery can be further improved.

[0138] On the other hand, if the weight average molecular weight of the copolymer is below the above upper limit, it is possible to give the functional layer more excellent adhesion. The reason is speculated to be that the solubility of the copolymer in the solvent is further improved, and a slurry composition that is more well dispersed by functional particles, etc. can be obtained. Therefore, when such a slurry composition is used for the formation of a functional layer, a functional layer that is more well dispersed by functional particles, etc. can be formed. In addition, since functional particles, etc. can be more well dispersed in the functional layer, the internal resistance of the all-solid-state secondary battery can be further reduced, and then the cycle characteristics of the all-solid-state secondary battery can be further improved.

[0139] In this specification, the "weight average molecular weight" can be measured using the method described in Examples.

[0140] [Molecular weight distribution] The molecular weight distribution of the copolymer is preferably 1.5 or more, more preferably 1.8 or more, and even more preferably 2.0 or more, and is preferably 6.0 or less, more preferably 5.0 or less, and even more preferably 4.0 or less.

[0141] If the molecular weight distribution of the copolymer is within the above range, it is possible to give the functional layer a more excellent adhesion. The reason is speculated to be that the solubility of the copolymer in the solvent is further improved, and a slurry composition that is more well dispersed by functional particles, etc. can be obtained. Therefore, when such a slurry composition is used for the formation of the functional layer, a functional layer that is more well dispersed by functional particles, etc. can be formed. In addition, since the functional particles, etc. can be more well dispersed in the functional layer, the internal resistance of the all-solid-state secondary battery can be further reduced, and the cycle characteristics of the all-solid-state secondary battery can be further improved.

[0142] In this specification, "molecular weight distribution" can be obtained by calculating the ratio of weight average molecular weight to number average molecular weight (weight average molecular weight / number average molecular weight). In addition, "number average molecular weight" can be measured as a standard polystyrene conversion value using gel permeation chromatography (GPC).

[0143] The weight average molecular weight and number average molecular weight of the copolymer can be controlled by, for example, the composition of the copolymer (the content ratio of each repeating unit), the molecular weight modifier added during polymerization, and the conditions of the copolymer preparation method (for example, polymerization temperature).

[0144] <<Content ratio of copolymer>> When the total of all components (including the solvent) in the adhesive composition is set to 100 mass %, the content ratio of the copolymer in the adhesive composition is preferably 1 mass % or more, more preferably 5 mass % or more, further preferably 8 mass % or more, preferably 30 mass % or less, more preferably 20 mass % or less, further preferably 15 mass % or less.

[0145] <Solvent> The solvent used in the adhesive composition of the present invention contains an ester solvent having 6 or more carbon atoms, and optionally contains other solvents compatible with the ester solvent having 6 or more carbon atoms (hereinafter, sometimes referred to as "other solvents"). Examples of other solvents include ester solvents having 5 or less carbon atoms, ketone solvents, alcohol solvents, and the like.

[0146] If a solvent containing an ester solvent having more than 6 carbon atoms is used, the haze of the copolymer solution can be well maintained. In addition, if a solvent containing an ester solvent having more than 6 carbon atoms is used, the generation of side reactions between the solvent and the functional particles can be suppressed, resulting in the ability to improve the cycle characteristics of the all-solid-state secondary battery.

[0147] Here, the ester solvent having 6 or more carbon atoms means that the total number of carbon atoms of the ester excluding the carbon atom of the carbonyl group is 6 or more. That is, the total number of carbon atoms of the organic group bonded to the carbon atom of the carbonyl group (hereinafter, sometimes referred to as "organic group A") and the number of carbon atoms of the organic group bonded to the non-carbonyl oxygen atom (hereinafter, sometimes referred to as "organic group B") is 6 or more. For example, isobutyl isobutyrate is an ester solvent having 7 carbon atoms because the organic group A has 3 carbon atoms and the organic group B has 4 carbon atoms. The organic group A and / or the organic group B are preferably hydrocarbon groups without substituents, and more preferably alkyl groups.

[0148] The number of carbon atoms in the ester solvent is not particularly limited as long as the haze of the copolymer solution is within a predetermined range, and may be, for example, 12 or less, or 10 or less.

[0149] Examples of the ester solvent having 6 or more carbon atoms include ethyl butyrate, butyl butyrate, isobutyl isobutyrate, amyl acetate, isoamyl acetate, ethyl hexanoate, octyl acetate, and amyl valerate. Among them, butyl butyrate, isobutyl isobutyrate, and octyl acetate are preferred, and butyl butyrate and isobutyl isobutyrate are more preferred.

[0150] The content of the ester solvent in the solvent is preferably 70% by mass or more, more preferably 80% by mass or more, further preferably 90% by mass or more, further preferably 95% by mass or more, further preferably 99% by mass or more, and particularly preferably 100%. That is, the solvent particularly preferably does not contain other solvents.

[0151] <Haze> In the adhesive composition of the present invention, when the copolymer is dissolved in a solvent in a manner such that the concentration of the copolymer is 8% by mass, the haze of the obtained copolymer solution is 30% or more and 80% or less. Moreover, the haze of the copolymer solution is preferably 40% or more, more preferably 50% or more, preferably 75% or less, and more preferably 70% or less.

[0152] If the haze of the copolymer solution is more than 30%, it is possible to give the functional layer excellent adhesion while reducing the internal resistance of the all-solid-state secondary battery. The reason is not clear, but it is presumed to be as described below. First, the haze of the copolymer solution is less than 30%, which means that most of the copolymer is dissolved in the solvent. Therefore, when using a binder composition comprising such a copolymer and a solvent, most of the surface of the functional particles is covered by the copolymer, and the functional particles are indirectly contacted with each other via the copolymer in the functional layer formed, as a result, the internal resistance of the all-solid-state secondary battery can be improved. On the other hand, it can be inferred that if the haze of the copolymer solution is more than 30% as in the binder composition of the present invention, the surface of the functional particles is appropriately covered by the copolymer, and the part of the functional particles directly contacting each other in the functional layer formed increases, as a result, the internal resistance of the all-solid-state secondary battery is reduced. In addition, it can be inferred that the balance between the part where the functional particles are indirectly contacted with each other via the copolymer and the part where the functional particles are directly contacted with each other in the functional layer is good, as a result, the excellent adhesion of the functional layer can be maintained.

[0153] On the other hand, if the haze of the copolymer solution is less than 80%, excellent adhesion can be imparted to the functional layer. The reason is presumed to be that the solubility of the copolymer in the solvent is improved, and a slurry composition well dispersed by functional particles can be obtained. Therefore, when such a slurry composition is used for the formation of a functional layer, a functional layer well dispersed by functional particles can be formed. In addition, since functional particles can be well dispersed in the functional layer, the internal resistance of the all-solid-state secondary battery can be reduced, and the cycle characteristics of the all-solid-state secondary battery can be improved.

[0154] The haze of the copolymer solution can be adjusted by the composition of the copolymer (the content ratio of each repeating unit), the type and weight average molecular weight of the solvent, and the conditions of the method for preparing the copolymer.

[0155] Moreover, from the perspective of being able to easily satisfy the above-mentioned haze requirement, the adhesive composition of the present invention particularly preferably comprises a copolymer and a solvent that are a combination of the following copolymer and a solvent, wherein the copolymer comprises a nitrile group-containing monomer unit, a conjugated diene monomer unit, an alkylene structural unit, and a C4-C9 (methyl)acrylate monomer unit, and when all repeating units in the copolymer are set to 100% by mass, the content of the nitrile group-containing monomer unit is greater than 10% by mass and less than 22% by mass (hereinafter sometimes referred to as "copolymer A"), and the solvent is a solvent composed of any one of butyl butyrate, isobutyl isobutyrate and octyl acetate (hereinafter sometimes referred to as "solvent A").

[0156] Furthermore, when the copolymer and the solvent are a combination of copolymer A and solvent A, the above-specified haze can be easily satisfied, and in addition, the internal resistance of the all-solid-state secondary battery can be particularly reduced while imparting particularly excellent adhesion to the functional layer for the all-solid-state secondary battery.

[0157] <Method for preparing binder composition for all-solid-state secondary battery> The adhesive composition can be prepared by dissolving or dispersing the above copolymer in a solvent containing an ester solvent having a carbon number of 6 or more. Specifically, the adhesive composition can be prepared by mixing the above copolymer and the solvent using a mixer such as a ball mill, a sand mill, a bead mill, a pigment disperser, a crusher, an ultrasonic disperser, a homogenizer, a planetary mixer, or a filmix.

[0158] In addition, when the copolymer is prepared as a dispersion liquid containing only another solvent, the copolymer is preferably subjected to solvent exchange to obtain the adhesive composition of the present invention. Here, the solvent exchange can be performed by a known method.

[0159] (Slurry composition for all-solid-state secondary battery) The slurry composition for all-solid-state secondary batteries of the present invention comprises functional particles and the binder composition of the present invention, and optionally further comprises a conductive material and other additives. That is, the slurry composition of the present invention at least comprises functional particles, the above-mentioned copolymer, and a solvent containing an ester solvent having a carbon number of 6 or more. In addition, the solvent contained in the slurry composition may all be a solvent from the binder composition, or may be a solvent newly added to the slurry composition differently from the solvent from the binder composition.

[0160] Since the binder composition of the present invention can reduce the internal resistance of the all-solid-state secondary battery and impart excellent adhesion to the functional layer, the slurry composition containing the binder composition can also reduce the internal resistance of the all-solid-state secondary battery and impart excellent adhesion to the functional layer.

[0161] <Functional particles> Functional particles are particles that can impart a predetermined function to a layer formed using a slurry composition. Here, the functional particles are preferably at least one of solid electrolyte particles and electrode active material particles. If the functional particles are at least one of solid electrolyte particles and electrode active material particles, the functional layer can be endowed with a function as a solid electrolyte layer and / or an electrode composite material layer.

[0162] Here, the slurry composition that can be used to form the solid electrolyte layer (hereinafter, sometimes referred to as "slurry composition for solid electrolyte layer") contains solid electrolyte particles, usually does not contain electrode active material particles, and preferably does not contain a conductive material.

[0163] In addition, the slurry composition that can be used in the formation of the electrode composite material layer (hereinafter, sometimes referred to as "slurry composition for electrode composite material layer") includes electrode active material particles (positive electrode active material particles, negative electrode active material particles), and optionally further includes solid electrolyte particles and conductive materials. More specifically, the slurry composition that can be used in the formation of the positive electrode composite material layer (hereinafter, sometimes referred to as "slurry composition for positive electrode composite material layer") includes positive electrode active material particles, and the slurry composition that can be used in the formation of the negative electrode composite material layer (hereinafter, sometimes referred to as "slurry composition for negative electrode composite material layer") includes negative electrode active material particles, and these slurry compositions optionally further include solid electrolyte particles and conductive materials.

[0164] <<Solid Electrolyte Particles>> Solid electrolyte particles usually use solid electrolytes obtained through a pulverization process, so they are granular, but not completely spherical but amorphous. Usually, the size of the particles can be measured by irradiating the particles with lasers and measuring the scattered light. In this case, the particle size is a value that assumes the shape of a particle to be spherical. When multiple particles are measured together, the existence ratio of particles of corresponding particle sizes can be expressed as a particle size distribution. Most of the solid electrolyte particles that form the solid electrolyte layer express the value measured by this method as an average particle size.

[0165] From the viewpoint of ion conduction resistance in the functional layer, the average particle size of the solid electrolyte particles is preferably 0.3 μm or more and 5.0 μm or less. In addition, the average particle size of the solid electrolyte particles is a volume average particle size, which refers to the particle size (D50) at which the cumulative volume calculated from the small diameter side is 50% in the particle size distribution (volume basis) measured by laser diffraction.

[0166] In the case of an all-solid-state lithium secondary battery, the solid electrolyte particles are not particularly limited as long as they have lithium ion conductivity, and preferably contain a crystalline inorganic lithium ion conductor or an amorphous inorganic lithium ion conductor.

[0167] Examples of crystalline inorganic lithium ion conductors include Li3N, LISICON (Li 14 Zn(GeO4)4), perovskite-type Li 0.5 La 0.5 TiO3、LIPON(Li 3+y PO 4-x N x)、Thio-LISICON(Li 3.25 Ge 0.25 P 0.75 S4) etc.

[0168] As an amorphous inorganic lithium ion conductor, a conductor (sulfide solid electrolyte material) containing S (sulfur atom) and having ion conductivity can be cited. Here, in the case where the all-solid-state secondary battery obtained using the slurry composition of the present invention is an all-solid-state lithium secondary battery, as the sulfide solid electrolyte material used, a sulfide solid electrolyte material formed using a raw material composition containing Li2S and sulfides of elements of groups 13 to 15 can be cited. As a method for synthesizing a sulfide solid electrolyte material using such a raw material composition, for example, an amorphization method can be cited. As an amorphization method, for example, a mechanical grinding method and a melt quenching method can be cited, among which a mechanical grinding method is preferred. This is because, by the mechanical grinding method, it is possible to treat at room temperature and seek to simplify the manufacturing process.

[0169] As the above-mentioned elements of Groups 13 to 15, for example, Al, Si, Ge, P, As, Sb, etc. can be cited. In addition, as sulfides of elements of Groups 13 to 15, specifically, Al2S3, SiS2, GeS2, P2S3, P2S5, As2S3, Sb2S3, etc. can be cited. Among them, it is preferred to use sulfides of Groups 14 or 15. In particular, the sulfide solid electrolyte material formed using a raw material composition containing Li2S and sulfides of elements of Groups 13 to 15 is preferably a Li2S-P2S5 material, a Li2S-SiS2 material, a Li2S-GeS2 material or a Li2S-Al2S3 material, and more preferably a Li2S-P2S5 material. This is because these have excellent Li ion conductivity.

[0170] In addition, the sulfide solid electrolyte material preferably has cross-linked sulfur. This is because the ion conductivity becomes higher by having cross-linked sulfur. It should be noted that "having cross-linked sulfur" can also be judged by considering the measurement results of Raman spectroscopy, the raw material composition ratio, the measurement results of NMR, etc.

[0171] From the viewpoint of being able to more reliably obtain a sulfide solid electrolyte material having cross-linked sulfur, the molar fraction of Li2S in the Li2S-P2S5 material or the Li2S-Al2S3 material is, for example, in the range of greater than 50% and less than 74%, preferably greater than 60% and less than 74%.

[0172] The sulfide solid electrolyte material may be sulfide glass or crystallized sulfide glass obtained by heat treating the sulfide glass. The sulfide glass may be obtained by, for example, the amorphization method described above. The crystallized sulfide glass may be obtained by, for example, heat treating the sulfide glass.

[0173] In particular, the sulfide solid electrolyte material is preferably composed of Li7P3S 11 This is because the Li ion conductivity is particularly excellent. 11 The method can be used to synthesize sulfide glass by, for example, mixing Li2S and P2S5 at a molar ratio of 70:30, amorphizing by a ball mill, and heat treating the obtained sulfide glass at a temperature of 150°C to 360°C to synthesize Li7P3S 11 .

[0174] In addition, as an amorphous inorganic lithium ion conductor, a substance containing O (oxygen atoms) and having ion conductivity (oxide solid electrolyte material) can also be used. Examples of oxide solid electrolyte materials include Li3N, LISICON (Li 14 Zn(GeO4)4), perovskite type (for example: Li 0.5 La 0.5 TiO3), garnet type (for example: Li7La3Zr2O 12 )、LIPON(Li 3+y PO 4-x N x )、Thio-LISICON(Li 3.25 Ge 0.25 P 0.75 S4) etc.

[0175] <<Electrode Active Material Particles>> The electrode active material particles generally include positive electrode active material particles and negative electrode active material particles. The positive electrode active material particles can be used in the slurry composition for the positive electrode composite material layer, and the negative electrode active material particles can be used in the slurry composition for the negative electrode composite material layer.

[0176] [Positive electrode active material particles] Positive electrode active material particles are particles composed of positive electrode active materials. In the case of an all-solid-state lithium secondary battery, the positive electrode active material is a compound that can intercalate and deintercalate lithium ions. Positive electrode active materials are roughly divided into positive electrode active materials composed of inorganic compounds and positive electrode active materials composed of organic compounds.

[0177] Examples of inorganic compounds include transition metal oxides, composite oxides of lithium and transition metals, and transition metal sulfides. As the above-mentioned transition metals, Fe, Co, Ni, Mn, and the like can be used. Specific examples of inorganic compounds include lithium-containing composite metal oxides such as LiCoO2, LiNiO2, LiMnO2, LiMn2O4, LiFePO4, and LiFeVO4; transition metal sulfides such as TiS2, TiS3, and amorphous MoS2; and Cu2V2O3, amorphous V2O-P2O5, MoO3, V2O5, and V6O. 13 These compounds may be partially element-substituted compounds.

[0178] Examples of the organic compound include polyaniline, polypyrrole, polyacene, disulfide compounds, polysulfide compounds, N-fluoropyridine, Salt, etc. The positive electrode active material may also be a mixture of the above-mentioned inorganic compound and organic compound.

[0179] From the perspective of improving battery characteristics such as load characteristics and cycle characteristics, and from the perspective of being able to obtain a fully solid electrolyte secondary battery with a large charge and discharge capacity, and from the perspective of easy processing of the slurry composition and the processing when manufacturing the positive electrode, the average particle size of the positive electrode active material particles is usually 0.1 μm or less and 50 μm or less, preferably 1 μm or less and 20 μm or less. The average particle size can be obtained by measuring the particle size distribution by laser diffraction.

[0180] [Negative electrode active material particles] Negative electrode active material particles are particles composed of negative electrode active materials. Examples of negative electrode active materials include carbon allotropes such as graphite and coke. Negative electrode active materials composed of the carbon allotropes can also be used in the form of a mixture or coating with metals, metal salts, oxides, etc. In addition, as negative electrode active materials, the following can be used: oxides and sulfates of silicon, tin, zinc, manganese, iron, nickel, etc.; metallic lithium; lithium alloys such as Li-Al, Li-Bi-Cd, and Li-Sn-Cd; lithium transition metal nitrides; silicon, etc. When using a metal material, a metal foil or metal plate can be used directly as an electrode, or a granular one can be used.

[0181] From the viewpoint of improving battery characteristics such as initial efficiency, load characteristics, and cycle characteristics, the average particle size of the negative electrode active material particles is usually 1 μm or more and 50 μm or less, and preferably 15 μm or more and 30 μm or less.

[0182] <Conductive Materials> The conductive material is generally a component that can be matched to promote electrical contact between functional particles in the electrode composite material layer. As the conductive material, conductive carbon materials such as carbon nanotubes, carbon black (e.g., acetylene black, Ketjen black (registered trademark), furnace black, etc.), graphite, carbon fibers other than carbon nanotubes, and carbon sheets; and fibers and foils of various metals can be used.

[0183] These can be used alone or in combination of two or more.

[0184] <Other additives> As other additives that may be contained in the slurry composition, reinforcing materials and the like are mentioned.

[0185] As the reinforcing material, various inorganic and organic fillers in the form of spheres, plates, rods or fibers can be used.

[0186] <Solid Content Concentration of Slurry Composition> The solid content concentration of the slurry composition for an all-solid-state secondary battery is preferably 30% by mass or more, more preferably 40% by mass or more, and is preferably 80% by mass or less, more preferably 70% by mass or less.

[0187] When the solid content concentration of the slurry composition for an all-solid-state secondary battery is within the above range, it is possible to effectively suppress the functional particles from falling off from the functional layer without inhibiting the battery reaction.

[0188] The solid content concentration of the slurry composition for a solid electrolyte layer is preferably 30 mass % or more, more preferably 40 mass % or more, preferably 80 mass % or less, more preferably 70 mass % or less, and further preferably 60 mass % or less.

[0189] When the solid content concentration of the slurry composition for a solid electrolyte layer is within the above range, it is possible to effectively suppress the solid electrolyte particles from falling off from the solid electrolyte layer without inhibiting the battery reaction.

[0190] The solid content concentration of the slurry composition for positive electrode composite material layer is preferably 30 mass % or more, more preferably 40 mass % or more, further preferably 50 mass % or more, and is preferably 80 mass % or less, more preferably 70 mass % or less.

[0191] When the solid content concentration of the slurry composition for the positive electrode mixture layer is within the above range, the positive electrode active material particles and the solid electrolyte particles can be effectively suppressed from falling off from the positive electrode mixture layer without inhibiting the battery reaction.

[0192] The solid content concentration of the slurry composition for negative electrode composite material layer is preferably 30 mass % or more, more preferably 40 mass % or more, further preferably 50 mass % or more, and is preferably 80 mass % or less, more preferably 70 mass % or less.

[0193] When the solid content concentration of the slurry composition for the negative electrode composite material layer is within the above range, it is possible to effectively suppress the negative electrode active material particles and the solid electrolyte particles from falling off from the negative electrode composite material layer without inhibiting the battery reaction.

[0194] <Content and mass ratio of each component> When the total solid content in the slurry composition for all-solid-state secondary batteries is set to 100 parts by mass, the content of the copolymer in the slurry composition for all-solid-state secondary batteries is preferably 0.1 parts by mass or more, more preferably 0.3 parts by mass or more, further preferably 0.5 parts by mass or more, preferably 10 parts by mass or less, more preferably 5 parts by mass or less, further preferably 2 parts by mass or less.

[0195] When the total solid content in the slurry composition for all-solid secondary batteries is 100 parts by mass, if the content of the copolymer in the slurry composition for all-solid secondary batteries is within the above range, the functional particles can be effectively suppressed from falling off from the functional layer without inhibiting the battery reaction.

[0196] When the total amount of solid components in the slurry composition for solid electrolyte layer is set to 100 parts by mass, the content of the copolymer in the slurry composition for solid electrolyte layer is preferably 0.1 parts by mass or more, more preferably 0.3 parts by mass or more, further preferably 0.5 parts by mass or more, preferably 10 parts by mass or less, more preferably 3 parts by mass or less, further preferably 1.5 parts by mass or less.

[0197] When the total solid content in the slurry composition for a solid electrolyte layer is 100 parts by mass, if the content of the copolymer in the slurry composition for a solid electrolyte layer is within the above range, the solid electrolyte particles can be effectively suppressed from falling off from the solid electrolyte layer without inhibiting the battery reaction.

[0198] When the total solid content in the slurry composition for positive electrode composite material layer is set to 100 parts by mass, the content of the copolymer in the slurry composition for positive electrode composite material layer is preferably 0.1 parts by mass or more, more preferably 0.3 parts by mass or more, further preferably 0.5 parts by mass or more, preferably 10 parts by mass or less, more preferably 3 parts by mass or less, and further preferably 1.5 parts by mass or less.

[0199] When the total solid content in the slurry composition for positive electrode composite material layer is set to 100 parts by mass, if the content of the copolymer in the slurry composition for positive electrode composite material layer is within the above range, the positive electrode active material particles and the solid electrolyte particles can be effectively suppressed from falling off from the positive electrode composite material layer without hindering the battery reaction.

[0200] When the total solid content in the slurry composition for negative electrode composite material layer is set to 100 parts by mass, the content of the copolymer in the slurry composition for negative electrode composite material layer is preferably 0.1 parts by mass or more, more preferably 0.5 parts by mass or more, further preferably 1 part by mass or more, preferably 10 parts by mass or less, more preferably 5 parts by mass or less, further preferably 2 parts by mass or less.

[0201] When the total solid content in the slurry composition for negative electrode composite material layer is set to 100 parts by mass, if the content of the copolymer in the slurry composition for negative electrode composite material layer is within the above range, the negative electrode active material particles and the solid electrolyte particles can be effectively suppressed from falling off from the negative electrode composite material layer without hindering the battery reaction.

[0202] When the total solid content in the slurry composition for all-solid-state secondary batteries is set to 100 parts by mass, the content of all functional particles in the slurry composition for all-solid-state secondary batteries is preferably 80 parts by mass or more, more preferably 90 parts by mass or more, further preferably 95 parts by mass or more, preferably 99.5 parts by mass or less, and more preferably 99 parts by mass or less.

[0203] When the total amount of solid components in the slurry composition for solid electrolyte layer is set to 100 parts by mass, the content of solid electrolyte particles in the slurry composition for solid electrolyte layer is preferably 80 parts by mass or more, more preferably 95 parts by mass or more, further preferably 97 parts by mass or more, preferably 99.5 parts by mass or less, and more preferably 99 parts by mass or less.

[0204] When the total solid content in the positive electrode composite material layer slurry composition is set to 100 parts by mass, the content of the positive electrode active material particles and the solid electrolyte particles in the positive electrode composite material layer slurry composition is preferably 80 parts by mass or more, more preferably 90 parts by mass or more, further preferably 95 parts by mass or more, preferably 99.5 parts by mass or less, and more preferably 98 parts by mass or less.

[0205] The mass ratio of the positive electrode active material particles to the solid electrolyte particles is preferably 90:10 to 50:50, more preferably 60:40 to 80:20.

[0206] If the mass ratio of the positive electrode active material particles is within the above range, the following phenomenon can be suppressed: due to the mass ratio of the positive electrode active material particles being too small, the mass of the positive electrode active material particles in the battery is reduced, resulting in a decrease in the capacity of the battery. In addition, the following phenomenon can be suppressed: due to the mass ratio of the solid electrolyte particles being too small, the conductivity cannot be fully obtained, the positive electrode active material particles cannot be effectively used, and the capacity of the battery is reduced.

[0207] When the total solid content in the negative electrode composite material layer slurry composition is set to 100 parts by mass, the content of the negative electrode active material particles and the solid electrolyte particles in the negative electrode composite material layer slurry composition is preferably 80 parts by mass or more, more preferably 90 parts by mass or more, further preferably 95 parts by mass or more, preferably 99.5 parts by mass or less, and more preferably 98 parts by mass or less.

[0208] The mass ratio of the negative electrode active material particles to the solid electrolyte particles is preferably negative electrode active material particles: solid electrolyte particles = 90:10 to 50:50, more preferably negative electrode active material particles: solid electrolyte particles = 60:40 to 80:20.

[0209] If the mass ratio of the negative electrode active material particles is within the above range, the following phenomenon can be suppressed: due to the ratio of the negative electrode active material particles being too small, the mass of the negative electrode active material particles in the battery is reduced, and the battery capacity is reduced. In addition, the following phenomenon can be suppressed: due to the ratio of the solid electrolyte particles being too small, sufficient conductivity cannot be obtained, and the negative electrode active material particles cannot be effectively used, resulting in a decrease in the battery capacity.

[0210] When the total solid content in the slurry composition for all-solid-state secondary batteries is set to 100 parts by mass, the content of the conductive material in the slurry composition for all-solid-state secondary batteries is preferably 0.5 parts by mass or more, more preferably 1 part by mass or more, further preferably 1.5 parts by mass or more, preferably 10 parts by mass or less, more preferably 5 parts by mass or less, further preferably 2.5 parts by mass or less.

[0211] <Method for preparing slurry composition for all-solid-state secondary battery> The above-mentioned slurry composition can be prepared by dissolving or dispersing the above-mentioned components in a solvent containing an ester solvent having a carbon number of 6 or more. For example, it is preferred that the functional particles, and optionally an additional solvent containing an ester solvent having a carbon number of 6 or more, a conductive material, other additives, etc. are added to the above-mentioned binder composition, and the mixture is mixed by the above-mentioned known method to prepare the slurry composition.

[0212] (Functional layer for all-solid-state secondary batteries) The all-solid-state secondary battery functional layer of the present invention is a layer formed using the secondary battery slurry composition of the present invention. That is, the all-solid-state secondary battery functional layer at least comprises a copolymer and functional particles. In addition, each component included in the functional layer is each component (solid content) included in the above-mentioned slurry composition, and the preferred existence ratio of these components is the same as the preferred existence ratio of each component (solid content) in the slurry composition.

[0213] The slurry composition of the present invention can reduce the internal resistance of the all-solid-state secondary battery and provide excellent adhesion to the functional layer. Therefore, the functional layer formed using the slurry composition can reduce the internal resistance of the all-solid-state secondary battery and exhibit excellent adhesion.

[0214] Here, when the functional layer is a solid electrolyte layer, the solid electrolyte layer contains a copolymer and solid electrolyte particles, and generally does not contain electrode active material particles, and preferably does not contain a conductive material.

[0215] Furthermore, when the functional layer is a positive electrode composite material layer, the positive electrode composite material layer contains a copolymer and positive electrode active material particles, and optionally further contains solid electrolyte particles and a conductive material.

[0216] Furthermore, when the functional layer is a negative electrode composite material layer, the negative electrode composite material layer contains a copolymer and negative electrode active material particles, and optionally further contains solid electrolyte particles and a conductive material.

[0217] The thickness of the functional layer is not particularly limited, but is preferably 20 μm or more, more preferably 40 μm or more, and further preferably 70 μm or more, and is preferably 200 μm or less, more preferably 150 μm or less, and further preferably 100 μm or less.

[0218] When the functional layer is a solid electrolyte layer, the thickness of the solid electrolyte layer is not particularly limited, but is preferably 20 μm or more, more preferably 40 μm or more, further preferably 70 μm or more, and preferably 200 μm or less.

[0219] When the functional layer is a positive electrode material layer, the thickness of the positive electrode material layer is not particularly limited, but is preferably 20 μm or more, more preferably 40 μm or more, and preferably 200 μm or less, more preferably 100 μm or less.

[0220] When the functional layer is a negative electrode composite material layer, the thickness of the negative electrode composite material layer is not particularly limited, but is preferably 20 μm or more, more preferably 40 μm or more, further preferably 70 μm or more, and preferably 200 μm or less, more preferably 150 μm or less.

[0221] <Method for forming a functional layer for an all-solid-state secondary battery> The functional layer can be formed on, for example, a substrate using the slurry composition of the present invention. Here, examples of the substrate include a current collector and an electrode.

[0222] Here, the method for forming the functional layer on the substrate using the slurry composition is not particularly limited, and examples thereof include: (A) A method of applying the slurry composition on the surface of a substrate and then drying it; (B) A method in which a slurry composition is applied onto a release substrate, dried to form a functional layer, and the obtained functional layer is transferred onto the substrate.

[0223] Here, the release substrate is not particularly limited, and a known release substrate such as an imide film can be used.

[0224] The method for applying the slurry composition to the substrate or the release substrate is not particularly limited, and examples thereof include a doctor blade method, a reverse roll method, a direct roll method, a gravure method, an extrusion method, and a brush coating method.

[0225] The method for drying the slurry composition on the substrate or the peeled substrate is not particularly limited, and a known method can be used, for example, drying using warm air, hot air, or low-humidity air; vacuum drying; and drying using irradiation of infrared rays, electron beams, etc. The drying conditions are not particularly limited, but the drying temperature is preferably 50 to 150° C., and the drying time is preferably 1 to 90 minutes.

[0226] (All-solid-state secondary battery) The all-solid-state secondary battery of the present invention has a functional layer for the all-solid-state secondary battery of the present invention. Specifically, the all-solid-state secondary battery of the present invention has a positive electrode having a positive electrode composite material layer on a current collector, a negative electrode having a negative electrode composite material layer on a current collector, and a solid electrolyte layer located between the positive electrode composite material layer and the negative electrode composite material layer, wherein at least any one layer, preferably all layers, of the positive electrode composite material layer, the negative electrode composite material layer, and the solid electrolyte layer are the functional layers of the present invention.

[0227] According to the above-mentioned all-solid-state secondary battery, it is possible to realize an all-solid-state secondary battery in which the battery materials are firmly bonded to each other while reducing the internal resistance.

[0228] <Solid electrolyte layer> About the composition of solid electrolyte layer, it has been described in the "all-solid-state secondary battery functional layer" project, so its record is omitted here. In addition, in the formation of positive electrode composite material layer and / or negative electrode composite material layer, when using the slurry composition of the present invention, a known solid electrolyte layer can be used as the solid electrolyte layer.

[0229] <Positive Electrode Composite Material Layer> About the composition of positive electrode composite material layer, it has been described in the "all-solid-state secondary battery functional layer" project, so its record is omitted here. In addition, in the formation of solid electrolyte layer and / or negative electrode composite material layer, when using the slurry composition of the present invention, known positive electrode composite material layer can be used as positive electrode composite material layer.

[0230] <Negative Electrode Composite Material Layer> About the composition of negative electrode composite material layer, it has been described in the "all-solid-state secondary battery functional layer" project, so its record is omitted here. In addition, in the formation of solid electrolyte layer and / or positive electrode composite material layer, when using the slurry composition of the present invention, a known negative electrode composite material layer can be used as the negative electrode composite material layer.

[0231] <Current collector> The current collector is not particularly limited as long as it is a material with electrical conductivity and electrochemical durability. From the viewpoint of heat resistance, metal materials such as iron, copper, aluminum, nickel, stainless steel, titanium, tantalum, gold, platinum, etc. are preferred. Among them, aluminum is particularly preferred as the positive electrode, and copper is particularly preferred as the negative electrode. The shape of the current collector is not particularly limited, and is preferably a sheet with a thickness of about 0.001 to 0.5 mm. In order to improve the bonding strength between the current collector and the positive and negative electrode composite material layer, it is preferred that the current collector be subjected to surface roughening treatment in advance before use. As surface roughening methods, mechanical polishing, electrolytic polishing, chemical polishing, etc. can be cited. In the mechanical polishing method, polishing cloth paper, whetstone, grinding wheel, wire brush with steel wire, etc., which are fixed with polishing agent particles, can be used.

[0232] <Thickness of Each Layer> The thickness of the functional layer in the all-solid-state secondary battery is not particularly limited, but is preferably 16 μm or more, more preferably 32 μm or more, further preferably 56 μm or more, and is preferably 160 μm or less, more preferably 120 μm or less, further preferably 80 μm or less.

[0233] The thickness of the solid electrolyte layer in the all-solid secondary battery is not particularly limited, but is preferably 16 μm or more, more preferably 32 μm or more, further preferably 56 μm or more, and preferably 160 μm or less.

[0234] The thickness of the positive electrode composite material layer in the all-solid-state secondary battery is not particularly limited, but is preferably 16 μm or more, more preferably 32 μm or more, and is preferably 160 μm or less, more preferably 80 μm or less.

[0235] The thickness of the negative electrode composite material layer in the all-solid-state secondary battery is not particularly limited, but is preferably 16 μm or more, more preferably 32 μm or more, further preferably 56 μm or more, and is preferably 160 μm or less, more preferably 120 μm or less.

[0236] <Method for manufacturing all-solid-state secondary battery> The all-solid-state battery can be manufactured by producing the positive electrode, the negative electrode, and the solid electrolyte layer in any method and order, and is not particularly limited.

[0237] Specifically, all-solid-state batteries can be manufactured by, for example, the following methods (a) to (d): (a) preparing a laminated body composed of a positive electrode composite material layer, a solid electrolyte layer and a negative electrode composite material layer laminated in sequence, and then attaching current collectors to both sides of the laminated body; (b) A method of laminating the positive electrode, negative electrode and solid electrolyte layer which are separately manufactured; (c) A method of forming a solid electrolyte layer on one electrode to produce an electrode with the solid electrolyte layer, and then laminating another electrode; (d) A method of preparing a laminate composed of a positive electrode composite material layer, a solid electrolyte layer, and a negative electrode composite material layer laminated in this order on one current collector, and then attaching another current collector thereto.

[0238] In addition, in the methods (a) to (d), the preparation of the laminate, the preparation of the electrode with the solid electrolyte layer, and the bonding of each layer to the current collector may be subjected to a pressing process. The pressure during the pressing process is preferably 100 MPa or more, more preferably 200 MPa or more, further preferably 300 MPa or more, preferably 700 MPa or less, more preferably 600 MPa or less, and further preferably 500 MPa or less.

[0239] Then, the element of the all-solid-state secondary battery obtained as above is placed in a battery container according to the battery shape in the original state or after winding, folding, etc., and sealed to obtain an all-solid-state secondary battery. In addition, as required, porous metal mesh, fuse, PTC element and other anti-overcurrent components, guide plates, etc. are placed in a battery container to prevent the pressure inside the battery from rising and overcharging and discharging. The shape of the battery can be any shape in a coin shape, button shape, sheet shape, cylindrical shape, square shape, flat shape, etc.

[0240] Example Hereinafter, the present invention will be specifically described based on Examples, but the present invention is not limited to these Examples. In addition, in the following description, "%" and "part" indicating an amount are based on mass unless otherwise specified.

[0241] In addition, unless otherwise specified, in a copolymer manufactured by copolymerizing a plurality of monomers, the ratio of a monomer unit formed by polymerizing a certain monomer in the copolymer is generally consistent with the ratio (addition ratio) of the certain monomer in all monomers used for the polymerization of the copolymer. In addition, in the case where the copolymer is a hydrogenated copolymer obtained by hydrogenating (hydrogenating) a copolymer containing a conjugated diene monomer unit, the total content ratio of the unhydrogenated conjugated diene monomer unit and the alkylene structural unit as the conjugated diene monomer unit after hydrogenation in the hydrogenated copolymer is consistent with the ratio (addition ratio) of the conjugated diene monomer in all monomers used for the polymerization of the copolymer.

[0242] In Examples and Comparative Examples, various measurements and evaluations were performed according to the following methods.

[0243] <Composition of copolymer> 100 g of the copolymer solution (adhesive composition) obtained in the examples and comparative examples was coagulated with 1 L of methanol and then vacuum dried at 60° C. for 12 hours. 1 H-NMR analysis was performed, and the content ratio (mass %) of each monomer unit and structural unit contained in the copolymer was calculated based on the obtained analysis value.

[0244] <Weight Average Molecular Weight and Molecular Weight Distribution of Copolymer> The weight average molecular weight (Mw) of the copolymer was measured by gel permeation chromatography (GPC) using a 10 mM LiBr-DMF solution under the following measurement conditions. In addition, the number average molecular weight (Mn) of the copolymer was measured in the same manner, and the molecular weight distribution (Mw / Mn) was calculated.

[0245] Separation column: Shodex KD-806M (manufactured by Showa Denko K.K.); Detector: Differential refractometer detector RID-10A (manufactured by Shimadzu Corporation); Flow rate of eluent: 0.3 mL / min; Column temperature: 40°C; · Standard polymer: TSK standard polystyrene (manufactured by Tosoh Corporation).

[0246] <THF-insoluble content of copolymer> The copolymer solution (adhesive composition) obtained in the examples and comparative examples is dried in an environment of 50% humidity and 23°C to 25°C to produce a film with a thickness of 3±0.3 mm. Next, the produced film is cut into 5 mm squares to prepare film sheets. About 1 g of these film sheets are accurately weighed, and the weight of the accurately weighed film sheets is taken as W0. Then, the accurately weighed film sheets are immersed in 100 g of THF (temperature 25°C) of the adhesive composition for 24 hours. After immersion for 24 hours, the film sheet is lifted out of THF, and the lifted film sheet is vacuum dried at 105°C for 3 hours, and its weight (the weight of the insoluble component) W1 is accurately weighed. Then, the THF insoluble component rate (%) is calculated according to the following formula.

[0247] THF insoluble component rate (%) = W1 / W0×100.

[0248] <Iodine value of copolymer> 100 g of the copolymer solution (adhesive composition) obtained in Examples and Comparative Examples was coagulated with 1 L of methanol and then vacuum dried at 60° C. for 12 hours. The iodine value of the obtained dry copolymer was measured in accordance with JIS K6235 (2006).

[0249] <Haze of Copolymer Solution (Adhesive Composition)> The solvent used in the preparation of the copolymer solution (binder composition) obtained in the embodiment and the comparative example was further added to adjust the concentration of the copolymer to 8% by mass. In addition, when the concentration of the copolymer in the copolymer solution was less than 8% by mass, the concentration of the copolymer was adjusted by evaporating the solvent, etc. In addition, when the solvent used in preparing the copolymer was different from the solvent of the binder composition, solvent exchange, etc. was performed.

[0250] Using a haze meter (product name "NDH7000SP", manufactured by Nippon Denshoku Industries, Ltd., an apparatus in accordance with JIS K 7136:2000), at 25°C, the solvent used in the preparation of the copolymer solution was added to a glass cuvette for liquid measurement, and after standard calibration, the copolymer solution with a concentration of 8% by mass obtained above was added to the glass cuvette to measure the haze of the copolymer solution.

[0251] <Adhesion of positive electrode composite material layer> The positive electrode obtained in the embodiment and the comparative example is cut into a rectangle of 1.0cm wide × 10cm long as a test piece. After affixing a transparent tape (transparent tape defined by JIS Z1522) on the side surface of the positive electrode composite material layer of the test piece, the transparent tape is peeled off from one end of the test piece at a speed of 50mm / min in a 180° direction to measure the stress at this time. A total of 3 measurements are performed, and the average value is obtained, which is used as the peel strength (N / m) and evaluated according to the following benchmarks. The greater the peel strength, the better the adhesion of the positive electrode composite material layer and the more firmly it adheres to the current collector.

[0252] A+: Peel strength is 3N / m or more; A: Peel strength is 2 N / m or more and less than 3 N / m; B: Peel strength is 1.5 N / m or more and less than 2 N / m; C: Peel strength is 1.5 N / m or more and less than 1 N / m; D: Peel strength is less than 1 N / m.

[0253] <Adhesion of negative electrode composite material layer> The negative electrode obtained in the embodiment and the comparative example was cut into a rectangle with a width of 1.0 cm and a length of 10 cm as a test piece. After affixing a transparent tape (transparent tape defined by JIS Z1522) on the side surface of the negative electrode composite material layer of the test piece, the transparent tape was peeled off from one end of the test piece at a speed of 50 mm / min in a 180° direction, and the stress at this time was measured. A total of 3 measurements were performed, and the average value was calculated, which was used as the peel strength (N / m) and evaluated according to the following benchmarks. The greater the peel strength, the better the adhesion of the negative electrode composite material layer and the more firmly it adheres to the current collector.

[0254] A+: Peel strength is 5N / m or more; A: Peel strength is 4 N / m or more and less than 5 N / m; B: Peel strength is 3 N / m or more and less than 4 N / m; C: Peel strength is 2 N / m or more and less than 3 N / m; D: Peel strength is less than 2 N / m.

[0255] <IV resistance of all-solid-state secondary battery> The all-solid-state secondary batteries obtained in the embodiments and comparative examples were charged to 50% SOC (State Of Charge) at 1C (C is the value represented by the rated capacity (mA) / 1h (hour)) in an atmosphere of 25°C. Next, with 50% SOC as the center, charging and discharging were performed for 30 seconds at 0.1C, 0.2C, 0.5C, 1C, and 2C, respectively. The battery voltage after 10 seconds on the discharge side was plotted against the current value, and its slope was calculated as the IV resistance (Ω) (IV resistance during discharge). The obtained IV resistance value (Ω) was evaluated according to the following criteria. The smaller the value of the IV resistance, the smaller the internal resistance of the all-solid-state secondary battery.

[0256] A: IV resistance is below 80Ω; B: IV resistance is greater than 80Ω and less than 90Ω; C: IV resistance is greater than 90Ω and less than 100Ω; D: IV resistance is greater than 100Ω.

[0257] <Cycling characteristics of all-solid-state secondary batteries> The all-solid-state secondary battery obtained in the embodiment and the comparative example was charged and discharged for 50 cycles as follows: charged from 3V to 4.2V at 0.2C at 25°C, and then discharged from 4.2V to 3V at 0.2C. The ratio of the 0.2C discharge capacity of the 50th cycle to the 0.2C discharge capacity of the first cycle was calculated as a percentage, and this value was used as the capacity retention rate, and evaluated according to the following criteria. The larger the value of the capacity retention rate, the less the discharge capacity decreases, and the better the cycle characteristics of the all-solid-state secondary battery.

[0258] A: The capacity retention rate is above 90%; B: The capacity retention rate is more than 80% and less than 90%; C: Capacity retention rate is above 70% and less than 80%; D: Capacity retention rate is less than 70%.

[0259] (Example 1) <Preparation of Copolymer Solution (Binder Composition)> 200 parts of ion exchange water, 2.5 parts of sodium dodecyl diphenyl ether sulfonate as an emulsifier, a monomer composition comprising 18 parts of acrylonitrile (nitrile-containing monomer), 42 parts of 1,3-butadiene (conjugated diene monomer), 35 parts of n-butyl acrylate (C4-C9 (meth) acrylate monomer), and 5 parts of 1,4-cyclohexanedimethanol monoacrylate (hydrophilic group-containing monomer), and 0.2 parts of tert-dodecyl mercaptan as a molecular weight regulator were added to the reactor. Then, 0.06 parts of cumene hydroperoxide and 0.025 parts of ferrous sulfate as a redox polymerization initiator containing an iron-based compound were added thereto to initiate emulsion polymerization of the monomer composition at 10°C. At the moment when the polymerization conversion rate reached 80%, 0.2 parts of hydroxylamine sulfate were added to every 100 parts of the monomer composition to terminate the polymerization.

[0260] After the polymerization is terminated, the obtained product is heated and steam distilled at 80°C under reduced pressure to remove unreacted monomers. Then, 2 parts of alkylated phenol as an antioxidant are added to the residual liquid to obtain a copolymer latex (aqueous dispersion of the granular copolymer before hydrogenation).

[0261] Then, 0.6 parts of a 10% aqueous solution of aluminum sulfate (coagulant) was added to 100 parts of the copolymer solid content in the obtained aqueous dispersion while stirring to coagulate the copolymer in the aqueous dispersion. Then, the dispersion was filtered and separated, and ion exchange water in an amount of 50 times that of the obtained filtrate was passed through the dispersion to wash the filtrate to obtain a copolymer before hydrogenation.

[0262] Next, the oil layer hydrogenation method is used as the hydrogenation method to hydrogenate the above-mentioned copolymer before hydrogenation. Specifically, first, the copolymer before hydrogenation is dissolved in acetone in a manner of 10% concentration to obtain an acetone solution of the hydrogenation object (copolymer before hydrogenation). The solution is injected into an autoclave, and a palladium-silicon dioxide catalyst of 500 mass ppm relative to 100% of the hydrogenation object is added to the solution. Then, the contents (solution) of the autoclave are heated to 50°C in a state pressurized to 3MPa with hydrogen. The temperature is maintained for 6 hours, and a hydrogenation reaction of the copolymer before hydrogenation is carried out to obtain a hydrogenation reaction product. After the hydrogenation reaction is terminated, the palladium-silicon dioxide catalyst is filtered to obtain the target copolymer (acetone solution).

[0263] Next, an appropriate amount of isobutyl isobutyrate is added to the obtained acetone solution of the copolymer to obtain a mixture. Then, vacuum distillation is performed at 80°C to remove acetone and excess isobutyl isobutyrate from the mixture, and solvent exchange is performed from acetone to isobutyl isobutyrate to obtain an isobutyl isobutyrate solution (binder composition) of the copolymer with a solid content concentration of 10% as a copolymer solution. Using the obtained copolymer solution (binder composition), the composition of the copolymer, the weight average molecular weight and molecular weight distribution of the copolymer, the THF insoluble component rate of the copolymer, the iodine value of the copolymer, and the haze of the copolymer solution are measured. The results are shown in Table 1.

[0264] <Preparation of Slurry Composition for Positive Electrode Composite Material Layer> 72 parts of lithium cobalt oxide (number average particle size: 11.5 μm) as positive electrode active material particles, 24.9 parts of sulfide glass composed of Li2S and P2S5 (Li2S / P2S5=70mol% / 30mol%, number average particle size: 0.9 μm) as inorganic solid electrolyte particles, 2.5 parts of acetylene black as a conductive material, and 0.6 parts (solid content equivalent) of the binder composition obtained as described above were mixed, and isobutyl isobutyrate was added as a solvent to adjust the solid content concentration to 80%, and then mixed for 60 minutes with a planetary mixer. Then, isobutyl isobutyrate was further added to adjust the solid content concentration to 60%, and mixed for 10 minutes to prepare a slurry composition for a positive electrode composite material layer.

[0265] <Preparation of Slurry Composition for Negative Electrode Composite Material Layer> 65 parts of graphite (number average particle size: 20 μm) as negative electrode active material particles, 32 parts of sulfide glass composed of Li2S and P2S5 (Li2S / P2S5=70 mol% / 30 mol%, number average particle size: 0.9 μm) as inorganic solid electrolyte particles, 1.5 parts of acetylene black as a conductive material, and 1.5 parts (solid content equivalent) of the binder composition obtained as described above were mixed, and isobutyl isobutyrate was added as a solvent to adjust the solid content concentration to 65%, and then mixed for 60 minutes with a planetary mixer. Then, isobutyl isobutyrate was further added to adjust the solid content concentration to 60%, and then mixed with a planetary mixer to prepare a slurry composition for a negative electrode composite material layer.

[0266] <Preparation of Slurry Composition for Solid Electrolyte Layer> In a glove box under an argon atmosphere (water concentration: 0.6ppm, oxygen concentration: 1.8ppm), 99.0 parts of sulfide glass composed of Li2S and P2S5 (Li2S / P2S5=70mol% / 30mol%, number average particle size: 0.9μm) as inorganic solid electrolyte particles were mixed with 1.0 parts (solid content equivalent) of the binder composition obtained as described above, and then isobutyl isobutyrate was added as a solvent to adjust the solid content concentration to 60%, and then mixed with a planetary mixer for 60 minutes. Then, isobutyl isobutyrate was further added to adjust the solid content concentration to 50%, and then mixed with a planetary mixer to prepare a slurry composition for a solid electrolyte layer.

[0267] <Production of positive electrode> The above-mentioned positive electrode composite material layer slurry composition was applied to the surface of the current collector (aluminum foil, thickness: 20 μm) and dried (temperature 120°C, 60 minutes) to form a positive electrode composite material layer with a thickness of 75 μm to obtain a positive electrode. The obtained positive electrode was used to evaluate the adhesion of the positive electrode composite material layer. The results are shown in Table 1.

[0268] <Production of negative electrode> The above-mentioned slurry composition for the negative electrode composite material layer was applied to the surface of the current collector (copper foil, thickness: 15 μm) and dried (temperature 120°C, 60 minutes) to form a negative electrode composite material layer with a thickness of 90 μm to obtain a negative electrode. The obtained negative electrode was used to evaluate the adhesion of the negative electrode composite material layer. The results are shown in Table 1.

[0269] <Manufacturing of all-solid-state secondary batteries> The solid electrolyte layer slurry composition is applied on the imide film (thickness: 25 μm) and dried (temperature 120°C, 60 minutes) to form a solid electrolyte layer with a thickness of 150 μm. The solid electrolyte layer on the imide film is bonded to the positive electrode in a manner that the solid electrolyte layer and the positive electrode composite material layer are in contact, and a pressing treatment is performed by applying a pressure of 400 MPa (pressing pressure) to transfer the solid electrolyte layer from the imide film to the positive electrode composite material layer, thereby obtaining a positive electrode with a solid electrolyte layer.

[0270] The above-mentioned positive electrode with a solid electrolyte layer is laminated to the negative electrode in such a way that the solid electrolyte layer of the positive electrode with a solid electrolyte layer is in contact with the negative electrode composite material layer of the negative electrode, and the solid electrolyte layer of the positive electrode with a solid electrolyte layer is pressed by applying a pressure of 400MPa (pressing pressure) to obtain an all-solid-state secondary battery (stacking order: aluminum foil / positive electrode composite material layer / solid electrolyte layer / negative electrode composite material layer / copper foil). The thickness of the solid electrolyte layer of the pressed all-solid-state secondary battery is 120μm. The IV resistance and cycle characteristics of the all-solid-state secondary battery are evaluated. The results are shown in Table 1.

[0271] (Example 2) In the preparation of the copolymer solution (adhesive composition), as a monomer composition, a composition containing 18 parts of acrylonitrile (nitrile group-containing monomer), 44 parts of 1,3-butadiene (conjugated diene monomer), 35 parts of n-butyl acrylate (C4-C9 (meth) acrylate monomer) and 3 parts of 2-hydroxyethyl methacrylate (hydrophilic group-containing monomer) was used, and various operations, measurements and evaluations were performed in the same manner as in Example 1. The results are shown in Table 1.

[0272] (Example 3) In the preparation of the copolymer solution (binder composition), as a monomer composition, a composition containing 15 parts of acrylonitrile (nitrile group-containing monomer), 40 parts of 1,3-butadiene (conjugated diene monomer), 30 parts of n-butyl acrylate (C4-C9 (meth) acrylate monomer), 5 parts of 1,4-cyclohexanedimethanol monoacrylate (hydrophilic group-containing monomer) and 10 parts of styrene (aromatic vinyl monomer) was used, and various operations, measurements and evaluations were performed in the same manner as in Example 1. The results are shown in Table 1.

[0273] (Example 4) In the preparation of the copolymer solution (binder composition), the preparation of the slurry composition for the positive electrode composite material layer, the preparation of the slurry composition for the negative electrode composite material layer, and the preparation of the slurry composition for the solid electrolyte layer, butyl butyrate was used instead of isobutyl isobutyrate. Except for this, various operations, measurements, and evaluations were performed in the same manner as in Example 1. The results are shown in Table 1.

[0274] (Example 5) In the preparation of the copolymer solution (adhesive composition), as a monomer composition, a composition containing 13 parts of acrylonitrile (nitrile group-containing monomer), 47 parts of 1,3-butadiene (conjugated diene monomer), 35 parts of n-butyl acrylate (C4-C9 (meth) acrylate monomer), and 5 parts of 1,4-cyclohexanedimethanol monoacrylate (hydrophilic group-containing monomer) was used, and various operations, measurements, and evaluations were performed in the same manner as in Example 1. The results are shown in Table 1.

[0275] (Example 6) In the preparation of the copolymer solution (adhesive composition), as a monomer composition, a composition containing 21 parts of acrylonitrile (nitrile group-containing monomer), 39 parts of 1,3-butadiene (conjugated diene monomer), 35 parts of n-butyl acrylate (C4-C9 (meth) acrylate monomer) and 5 parts of 1,4-cyclohexanedimethanol monoacrylate (hydrophilic group-containing monomer) was used, and various operations, measurements and evaluations were performed in the same manner as in Example 1. The results are shown in Table 1.

[0276] (Example 7) In the preparation of the copolymer solution (binder composition), various operations, measurements, and evaluations were performed in the same manner as in Example 1, except that the polymerization temperature of the emulsion polymerization was changed from 10° C. to 8° C. The results are shown in Table 1.

[0277] (Example 8) In the preparation of the copolymer solution (binder composition), various operations, measurements, and evaluations were performed in the same manner as in Example 1, except that the polymerization temperature of the emulsion polymerization was changed from 10° C. to 15° C. The results are shown in Table 1.

[0278] (Example 9) In the preparation of the copolymer solution (binder composition), the preparation of the slurry composition for the positive electrode composite material layer, the preparation of the slurry composition for the negative electrode composite material layer, and the preparation of the slurry composition for the solid electrolyte layer, octyl acetate was used instead of isobutyl isobutyrate, and other operations, measurements, and evaluations were performed in the same manner as in Example 1. The results are shown in Table 1.

[0279] (Example 10) In the preparation of the copolymer solution (adhesive composition), as a monomer composition, a composition containing 18 parts of acrylonitrile (nitrile group-containing monomer), 32 parts of 1,3-butadiene (conjugated diene monomer), 45 parts of n-butyl acrylate (C4-C9 (meth) acrylate monomer) and 5 parts of 1,4-cyclohexanedimethanol monoacrylate (hydrophilic group-containing monomer) was used, and various operations, measurements and evaluations were performed in the same manner as in Example 1. The results are shown in Table 1.

[0280] (Example 11) In the preparation of the copolymer solution (adhesive composition), as a monomer composition, a composition containing 18 parts of acrylonitrile (nitrile group-containing monomer), 52 parts of 1,3-butadiene (conjugated diene monomer), 25 parts of n-butyl acrylate (C4-C9 (meth) acrylate monomer), and 5 parts of 1,4-cyclohexanedimethanol monoacrylate (hydrophilic group-containing monomer) was used, and various operations, measurements, and evaluations were performed in the same manner as in Example 1. The results are shown in Table 1.

[0281] (Example 12) The various operations, measurements, and evaluations were performed in the same manner as in Example 1 except that the amount of the palladium-silica catalyst used was changed from 500 mass ppm to 200 mass ppm in the preparation of the copolymer solution (binder composition).

[0282] (Example 13) The various operations, measurements, and evaluations were performed in the same manner as in Example 1, except that the amount of the palladium-silica catalyst used was changed from 500 mass ppm to 2000 mass ppm in the preparation of the copolymer solution (binder composition).

[0283] (Example 14) In the preparation of the copolymer solution (adhesive composition), as a monomer composition, a composition containing 17 parts of acrylonitrile (nitrile group-containing monomer), 48 parts of 1,3-butadiene (conjugated diene monomer), and 35 parts of n-butyl acrylate (C4-C9 (meth) acrylate monomer) was used, and various operations, measurements, and evaluations were performed in the same manner as in Example 1. The results are shown in Table 1.

[0284] (Example 15) In the preparation of the copolymer solution (adhesive composition), as a monomer composition, a composition containing 15 parts of acrylonitrile (nitrile group-containing monomer), 49 parts of 1,3-butadiene (conjugated diene monomer), 30 parts of n-butyl acrylate (C4-C9 (meth) acrylate monomer), 4 parts of 1,4-cyclohexanedimethanol monoacrylate (hydrophilic group-containing monomer) and 2 parts of methacrylic acid (hydrophilic group-containing monomer) was used, and various operations, measurements and evaluations were performed in the same manner as in Example 1. The results are shown in Table 1.

[0285] (Comparative Example 1) In the preparation of the copolymer solution (adhesive composition), as a monomer composition, a composition containing 8 parts of acrylonitrile (nitrile group-containing monomer), 52 parts of 1,3-butadiene (conjugated diene monomer), 35 parts of n-butyl acrylate (C4-C9 (meth) acrylate monomer) and 5 parts of 1,4-cyclohexanedimethanol monoacrylate (hydrophilic group-containing monomer) was used, and various operations, measurements and evaluations were performed in the same manner as in Example 1. The results are shown in Table 1.

[0286] (Comparative Example 2) In the preparation of the copolymer solution (adhesive composition), as a monomer composition, a composition containing 28 parts of acrylonitrile (nitrile group-containing monomer), 32 parts of 1,3-butadiene (conjugated diene monomer), 35 parts of n-butyl acrylate (C4-C9 (meth) acrylate monomer) and 5 parts of 1,4-cyclohexanedimethanol monoacrylate (hydrophilic group-containing monomer) was used, and various operations, measurements and evaluations were performed in the same manner as in Example 1. The results are shown in Table 1.

[0287] (Comparative Example 3) In the preparation of the copolymer solution (binder composition), various operations, measurements, and evaluations were performed in the same manner as in Example 1, except that the polymerization temperature of the emulsion polymerization was changed from 10° C. to 6° C. The results are shown in Table 1.

[0288] (Comparative Example 4) In the preparation of the copolymer solution (adhesive composition), various operations, measurements, and evaluations were performed in the same manner as in Example 1, except that the polymerization temperature of the emulsion polymerization was changed from 10° C. to 20° C. The results are shown in Table 1.

[0289] (Comparative Example 5) In the preparation of the copolymer solution (binder composition), the preparation of the slurry composition for the positive electrode composite material layer, the preparation of the slurry composition for the negative electrode composite material layer, and the preparation of the slurry composition for the solid electrolyte layer, xylene was used instead of isobutyl isobutyrate, and other operations, measurements, and evaluations were performed in the same manner as in Example 1. The results are shown in Table 1.

[0290] (Comparative Example 6) In the preparation of the copolymer solution (binder composition), the preparation of the slurry composition for the positive electrode composite material layer, the preparation of the slurry composition for the negative electrode composite material layer, and the preparation of the slurry composition for the solid electrolyte layer, cyclopentyl methyl ether was used instead of isobutyl isobutyrate, and other operations, measurements, and evaluations were performed in the same manner as in Example 1. The results are shown in Table 1.

[0291] It should be noted that in Table 1, The "C4-C9 (meth)acrylate monomer unit" refers to a (meth)acrylate monomer unit having an alkyl group having 4 or more and 9 or less carbon atoms. "AN" stands for acrylonitrile unit, "BD" represents 1,3-butadiene units, "H-BD" represents 1,3-butadiene hydride unit, "BA" represents n-butyl acrylate unit, "CHDMMA" means 1,4-cyclohexanedimethanol monoacrylate units, "HEMA" means 2-hydroxyethyl methacrylate units, "MAA" means methacrylic acid units, "St" represents a styrene unit, "CPME" means cyclopentyl methyl ether.

[0292] [Table 1] .

[0293] As is clear from Table 1, in Examples 1 to 15, the internal resistance of the all-solid-state secondary battery is reduced, and the functional layer for the all-solid-state secondary battery has excellent adhesion.

[0294] Industrial Applicability According to the present invention, it is possible to provide an adhesive composition for an all-solid-state secondary battery that can reduce the internal resistance of the all-solid-state secondary battery and impart excellent adhesion to a functional layer for the all-solid-state secondary battery.

[0295] Furthermore, according to the present invention, it is possible to provide a slurry composition for an all-solid-state secondary battery that can reduce the internal resistance of the all-solid-state secondary battery and impart excellent adhesion to the functional layer for the all-solid-state secondary battery.

[0296] Furthermore, according to the present invention, it is possible to provide a functional layer for an all-solid-state secondary battery that can reduce the internal resistance of the all-solid-state secondary battery and exhibit excellent adhesiveness.

[0297] Furthermore, according to the present invention, it is possible to provide an all-solid-state secondary battery in which battery materials are firmly bonded to each other while reducing internal resistance.

Claims

1. A binder composition for an all-solid-state secondary battery, comprising a copolymer and a solvent, wherein the copolymer contains a nitrile-containing monomer unit, The solvent contains an ester solvent having 6 or more carbon atoms, When all repeating units in the copolymer are set to 100% by mass, the content ratio of the nitrile group-containing monomer unit in the copolymer is 10% by mass or more and 22% by mass or less, The copolymer has a tetrahydrofuran-insoluble content of 0.5% by mass or more and 3% by mass or less, When the copolymer is dissolved in the solvent so that the concentration of the copolymer becomes 8% by mass, the haze of the obtained copolymer solution is 30% or more and 80% or less.

2. The binder composition for an all-solid-state secondary battery according to claim 1, wherein The iodine value of the copolymer is 0.5 mg / 100 mg or more and 30 mg / 100 mg or less.

3. The binder composition for an all-solid-state secondary battery according to claim 1 or 2, wherein: The copolymer also contains alkylene structural units, The alkylene structural unit is a 1,3-butadiene hydride unit, The nitrile group-containing monomer unit is an acrylonitrile unit.

4. The binder composition for an all-solid-state secondary battery according to any one of claims 1 to 3, wherein The copolymer contains a (meth)acrylate monomer unit having an alkyl group having 4 to 9 carbon atoms.

5. The binder composition for an all-solid-state secondary battery according to claim 4, wherein: When all repeating units in the copolymer are taken as 100 mass %, the content ratio of the (meth)acrylate monomer unit having an alkyl group having 4 to 9 carbon atoms in the copolymer is 25 to 45 mass %.

6. The binder composition for an all-solid-state secondary battery according to any one of claims 1 to 5, wherein The copolymer has a hydrophilic group. 7 . A slurry composition for an all-solid-state secondary battery, comprising functional particles and the binder composition for an all-solid-state secondary battery according to claim 1 .

8. The slurry composition for an all-solid-state secondary battery according to claim 7, wherein The functional particles are at least any one of solid electrolyte particles and electrode active material particles. 9 . A functional layer for an all-solid-state secondary battery, which is formed using the slurry composition for an all-solid-state secondary battery according to claim 7 or 8 . 10 . An all-solid-state secondary battery comprising the functional layer for an all-solid-state secondary battery according to claim 9 .

Citation Information

Patent Citations

  • Holding device for optical shutter element

    JP1982068815A

  • Cathode for all-solid-state lithium-ion battery and all-solid-state lithium-ion battery including said cathode

    JP2020525992A